Hadith #142 - Sahih Muslim - Anas (Sahih Muslim)
The love of the Ansar is the sign of faith and hatred against them is the sign of dissemblance.
Grade: Sahih

Hadith #166 - Sahih Muslim - Anas (Sahih Muslim)
Associating anyone with Allah, disobedience to parents, killing a person and false utterance.
Grade: Sahih

Hadith #221 - Sahih Muslim - Anas (Sahih Muslim)
â O ye who believe I raise not your voices above the voice of the Prophet, nor shout loud unto him in discourse, as ye shout loud unto one another, lest your deeds should become null and void, while you perceive notâ (xlix. 2-5), was revealed. Thabit b. Qais confined himself in his house and said: I am one of the denizens of Fire, and he deliberately avoided coming to the Apostle (ï·º). The Apostle (ï·º) asked Saâd b, Muâadh about him and said, Abu Amr, how is Thabit? Has he fallen sick?
Grade: Sahih

Hadith #222 - Sahih Muslim - Anas (Sahih Muslim)
Thabit b. Qais was the orator of the Ansar, when this verse was revealed: the rest of the hadith is the same with the exception that there is no mention of Saâd b. Muâadh in it.
Grade: Sahih

Hadith #224 - Sahih Muslim - Anas (Sahih Muslim)
We observed a man, one of the dwellers of Paradise, walking about amongst us.
Grade: Sahih

Hadith #258 - Sahih Muslim - Anas (Sahih Muslim)
Verily your people would constantly question about this and that till they would say: Well, it is Allah Who created the creation, but who created Allah?
Grade: Sahih

Hadith #282 - Sahih Muslim - Anas (Sahih Muslim)
âThe Hour (Resurrection) will not occur until âAllah, Allahâ is not said on earth.â
Grade: Sahih

Hadith #283 - Sahih Muslim - Anas (Sahih Muslim)
âThe Hour (Resurrection) will not occur as long as anyone says: âAllah, Allah.'â
Grade: Sahih

Hadith #316 - Sahih Muslim - Anas (Sahih Muslim)
I was brought al-Buraq Who is an animal white and long, larger than a donkey but smaller than a mule, who would place his hoof a distance equal to the range of version. I mounted it and came to the Temple (Bait Maqdis in Jerusalem), then tethered it to the ring used by the prophets. I entered the mosque and prayed two rakâahs in it, and then came out and Gabriel brought me a vessel of wine and a vessel of milk. I chose the milk, and Gabriel said: You have chosen the natural thing. Then he took
Grade: Sahih

Hadith #318 - Sahih Muslim - Anas (Sahih Muslim)
That was the part of Satan in thee. And then he washed it with the water of Zamzam in a golden basin and then it was joined together and restored to it place. The boys came running to his mother, i. e. his nurse, and said: Verily Muhammad has been murdered. They all rushed toward him (and found him all right) His color was changed, Anas said. I myself saw the marks of needle on his breast.
Grade: Sahih

Hadith #319 - Sahih Muslim - Anas (Sahih Muslim)
Three beings (angels) came to him in the mosque of the Kaâbah, while he was sleeping in the sacred mosque before it (the Command of Night Journey and Accension) was revealed to him. The rest of the hadith is narrated like that of Thabit. However, some portions have occurred before and some of them have occurred after; some have been added and some deleted.
Grade: Sahih

Hadith #320 - Sahih Muslim - Anas (Sahih Muslim)
Abu Dharr used to relate that the Messenger of Allah (ï·º) said: The roof of my house was cleft when I was in Mecca and Gabriel descended and opened my heart and then washed it with the water of Zamzam. He then brought a gold basin full of wisdom and faith and after emptying it into my breast, he closed it up. Then taking me by he hand, he ascended with me to th heaven, and when we came to the lowest heaven, Gabriel said to the guardian of the lowest heaven: Open. He asked who was there? He repl
Grade: Sahih

Hadith #321 - Sahih Muslim - Anas (Sahih Muslim)
I was near the House (i. e. Kaâbah) in a state between sleep and wakefulness when I heard someone say: He is the third among the two persons. Then he came to me and took me with him. Then a golden basin containing the water of Zamzam was brought to me and my heart was opened up to such and such (part). Qatada said: I asked him who was with me (i e. the narrator) and what he meant by such and such (part). He replied: (It means that it was opened) up to the lower part of his abdomen (Then the ha
Grade: Sahih

Hadith #380 - Sahih Muslim - Anas (Sahih Muslim)
Four persons would be brought out from the Fire and would be presented to Allah. One of them would turn (towards the He) ) ) and say: O my Lord, when Thou hast brought me out from it, do not throw me back into it, and Allah would rescue him from it.
Grade: Sahih

Hadith #381 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: Allah would gather people on the Day of Resurrection and they would be concerned about it, and Ibn Ubaid said. They would get a Divine inspiration about it, and would say: If we could seek intercession with our Lord, we may be relieved from this predicament of ours. He (the Holy Prophet) said: They would come to Adam andsay, Thou art Adam, the father of mankind. Allah created thee with His own hand and breathed unto thee of His Spirit and commanded the angels a
Grade: Sahih

Hadith #382 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: The believers would gather on the Day of Resurrection, and they would be concerned about it, or would be made mindful of it (i. e. the trjuble for it), (and the remaining part of the hadith w, ) uld be narrated) like the one transmitted by Abu Uwana, and he said in the hadith: Then I would come for the fourth time, or I would return the fourth time, and would say: O my Lord, no one has been left but he whom the Holy Qurâan has restrained.
Grade: Sahih

Hadith #383 - Sahih Muslim - Anas (Sahih Muslim)
The Prophet of Allah (may peace be, upon him) said: Allah will gather the believers on the Day of Resurrection and they would be made mindful of it; and the rest (of the hadith) is like the one narrated above; and then he mentioned the fourth time: And I (the Holy Prophet) would say: O my Lord, no one is left in the Fire except he whom the Qurâan has restrained, i e. eternally doomed.
Grade: Sahih

Hadith #384 - Sahih Muslim - Anas (Sahih Muslim)
Verily the Apostle (ï·º) said: He who professed: There is no god but Allah, would be brought out of the Fire even though he has in his heart virtue equal to the weight of a barley grain. Then he who professed: There is no god but Allah, would come out of the Fire, even though he has in his heart virtue equal to the weight of a wheat grain. He would then bring out from the Fire he who professed: There is no god but Allah, even though he has in his heart virtue equal to the weight of an atom. Ibn
Grade: Sahih

Hadith #389 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: I would be the first among people to intercede in the Paradise and amongst the apostles I would have the largest following (on the Day of Resurrection).
Grade: Sahih

Hadith #390 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: Amongst the apostles I would have the largest following on the Day of Resurrec tion, and I would be the first to knock at the door of Paradise.
Grade: Sahih

Hadith #391 - Sahih Muslim - Anas (Sahih Muslim)
The Apostle of Allah (ï·º) said: I would be the first intercessor in the Paradise and no apostle amongst the apostles has been testified (by such a large number of people) as I have been testified. And verily there woald be an apostle among the apostles who would be testified to by only one man from his people.
Grade: Sahih

Hadith #392 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: I will come to the gate of Paradise on the Day of Resurrection. and would seek its opening. and the keeper would say: Who art thou? I would say: Muhammad. He would then say: It is for thee that I have been ordered, and not to open it for anyone before thee.
Grade: Sahih

Hadith #400 - Sahih Muslim - Anas (Sahih Muslim)
Verily the Messenger of Allah (ï·º) said: There is for every apostle a prayer with which he prays (to Allah) for his Ummah. I have reserved my prayer for the intercession of my Ummah on the Day of Resurrection.
Grade: Sahih

Hadith #406 - Sahih Muslim - Anas (Sahih Muslim)
Verily, a person said: Messenger of Allah, where is my father? He said: (He) is in the Fire. When he turned away, he (the Holy Prophet) called him and said: Verily my father and your father are in the Fire.
Grade: Sahih

Hadith #505 - Sahih Muslim - Anas (Sahih Muslim)
A time limit has been prescribed for us for clipping the moustache, cutting the nails, plucking hair under the armpits, shaving the pubes, that it should not be neglected far more than forty nights.
Grade: Sahih

Hadith #525 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) entered an enclosure while a servant was following him with a jar of water and he was the youngest amongst us and he placed it by the side of a lote-tree. When the Messenger of Allah, (ï·º) relieved himself, he came out and had cleansed himself with water.
Grade: Sahih

Hadith #526 - Sahih Muslim - Anas (Sahih Muslim)
When the Messenger of Allah (ï·º) entered the privy, a servant and I used to carry a skin of water, and a pointed staff, and he would cleanse himself with water.
Grade: Sahih

Hadith #527 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) went to a far-off place in the desert (hidden from the sight of human beings) for relieving himself. Then I brought water for him and he cleansed himself.
Grade: Sahih

Hadith #564 - Sahih Muslim - Anas (Sahih Muslim)
A Bedouin urinated in the mosque. Some of the persons stood up (to reprimand him or to check him from doing so), but the Messenger of Allah (ï·º) said: Leave him alone; donât interrupt him. He (the narrator) said: And when he had finished, he called for a bucket of water and poured it over.
Grade: Sahih

Hadith #565 - Sahih Muslim - Anas (Sahih Muslim)
Leave him alone. When he had finished, the Messenger of Allah (ï·º) ordered that a bucket (of water) should be brought and poured over it.
Grade: Sahih

Hadith #566 - Sahih Muslim - Anas (Sahih Muslim)
While we were in the mosque with Allahâs Messenger (ï·º), a desert Arab came and stood up and began to urinate in the mosque. The Companions of Allahâs Messenger (ï·º) said: Stop, stop, but the Messenger of Allah (ï·º) said: Donât interrupt him; leave him alone. They left him alone, and when he finished urinating, Allahâs Messenger (ï·º) called him and said to him: These mosques are not the places meant for urine and filth, but are only for the remembrance of Allah, prayer and the recita
Grade: Sahih

Hadith #613 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) used to have sexual intercourse with his wives with a single bath.
Grade: Sahih

Hadith #614 - Sahih Muslim - Anas (Sahih Muslim)
Umm Sulaim who was the grandmother of Ishaq came to the Messenger of Allah (ï·º) in the presence of âAâisha and said to him: Messenger of Allah, in case or woman sees what a man sees in dream and she experiences in dream what a man experiences (i. e. experiences orgasm)? Upon this âAâisha remarked: O Umm Sulaim, you brought humiliation to women;may your right hand be covered with dust. He (the Holy Prophet) said to âAâisha: Let your hand be covered with dust, and (addressing Umm Sula
Grade: Sahih

Hadith #615 - Sahih Muslim - Anas (Sahih Muslim)
In case a woman sees that, she must take a bath. Umm Sulaim said: I was bashful on account of that and said: Does it happen? Upon this the Messenger of Allah (ï·º) said: Yes (it does happen), otherwise how can (a child) resemble her? Manâs discharge (i. e. sperm) is thick and white and the discharge of woman is thin and yellow; so the resemblance comes from the one whose genes prevail or dominate.
Grade: Sahih

Hadith #616 - Sahih Muslim - Anas (Sahih Muslim)
A woman asked the Messenger of Allah (way peace be upon him) about a woman who sees in her dream what a man sees in his dream (sexual dream). He (the Holy Prophet) said: If she experiences what a man experiences, she should take a bath.
Grade: Sahih

Hadith #642 - Sahih Muslim - Anas (Sahih Muslim)
The Apostle of Allah (ï·º) performed ablution with one Mudd and took bath with a Saâ up to five Mudds.
Grade: Sahih

Hadith #735 - Sahih Muslim - Anas (Sahih Muslim)
When the Messenger of Allah (ï·º) entered the privy, and in the hadith transmitted by Hushaim (the words are): When the Messenger of Allah (ï·º) entered the lavatory, be used to say: O Allah, I seek refuge in Thee from wicked and noxious things.
Grade: Sahih

Hadith #737 - Sahih Muslim - Anas (Sahih Muslim)
(The people) stood up for prayer and the Messenger of Allah (ï·º) was whispering to a man, and in the narration of âAbd al-Warith (the words are): The Apostle of Allah (ï·º) was having a private conversation with a man, and did not start the prayer till the people dozed off.
Grade: Sahih

Hadith #738 - Sahih Muslim - Anas (Sahih Muslim)
(The people) stood up for prayer and the Messenger of Allah (ï·º) was talking in whispers with a man, and he did not discontinue the conversation till his Companions dozed off; he then came and led the prayer.
Grade: Sahih

Hadith #740 - Sahih Muslim - Anas (Sahih Muslim)
(The people) stood up for the night prayer when a man spoke forth: I need to say something. The Apostle of Allah (ï·º) entered into secret conversation with him, till the people dozed off or some of the people (dozed off), and then they said the prayer.
Grade: Sahih

Hadith #742 - Sahih Muslim - Anas (Sahih Muslim)
Bilal was commanded (by the Messenger of Allah) to repeat (the phrases of) Adhan twice and once in Iqama. The narrator said: I made a mention of it before Ayyub who said: Except for saying: Qamat-is-Salat .
Grade: Sahih

Hadith #743 - Sahih Muslim - Anas (Sahih Muslim)
They (the Companions) discussed that they should know the timings of prayer by means of something recognized by all. Some of them said that fire should be lighted or a bell should be rung. But Bilal was ordered to repeat the phrases twice in Adhan, and once in Iqama.
Grade: Sahih

Hadith #745 - Sahih Muslim - Anas (Sahih Muslim)
Bilal was commanded (by the Holy Prophet) to repeat the phrases twice in Adhan, and once in lqama.
Grade: Sahih

Hadith #751 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) used to attack the enemy when it was dawn. He would listen to the Adhan; so if he heard an Adhan, he stopped, otherwise made an attack. Once on hearing a man say: Allah is the Greatest, Allah is the Greatest, the Messenger of Allah (ï·º) remarked: He is following al-Fitra (al-Islam). Then hearing him say: I testify that there is no god but Allah. there is no god but Allah, the Messenger of Allah (ï·º) said: You have come out of the Fire (of Hell). They looked at him
Grade: Sahih

Hadith #792 - Sahih Muslim - Anas (Sahih Muslim)
I observed prayer along with the Messenger of Allah (ï·º) and with Abu Bakr, Umar and Uthman (may Allah be pleased with all of them), but I never heard any one of them reciting Bismillah-ir-Rahman-ir-Rahim loudly.
Grade: Sahih

Hadith #796 - Sahih Muslim - Anas (Sahih Muslim)
One day the Messenger of Allah (ï·º) was sitting amongst us that he dozed off. He then raised his head smilingly. We said: What makes you smile. Messenger of Allah? He said: A Sura has just been revealed to me, and then recited: In the name of Allah, the Compassionate, the Merciful. Verily We have given thee Kauthar (fount of abundance). Therefore turn to thy Lord for prayer and offer sacrifice, and surely thy enemy is cut off (from the good). Then he (the Holy Prophet) said: Do you know what Ka
Grade: Sahih

Hadith #823 - Sahih Muslim - Anas (Sahih Muslim)
The Apostle of Allah (ï·º) fell down from a horse and his right side was grazed. We went to him to inquire after his health when the time of prayer came. He led us in prayer in a sitting posture and we said prayer behind him sitting, and when he finished the prayer hesaid: The Imam is appointed only to be followed; so when he recites takbir, you should also recite that; when he prostrates, you should also prostrate; when he rises up, you should also rise up, and when he saidâ God listens to hi
Grade: Sahih

Hadith #824 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) fell down from a horse and he was grazed and he led the prayer for us sitting, and the rest of the hadith is the same.
Grade: Sahih

Hadith #825 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) fell down from a horse and his right side was grazed, and the rest of the hadith is the same with the addition of these words:â When he (the Imam) says prayer standing, you should also do so.â
Grade: Sahih

Hadith #826 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) rode a horse and fell down from it and his right side was grazed, and the rest of the hadith is the same, and (these words) are found in it:â When he (the Imam) says prayer in an erect posture, you should also say it in an erect posture.â
Grade: Sahih

Hadith #827 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) fell down from his horse and his right side was grazed, and the rest of the hadith is the same. In this hadith there are no additions (of words) as transmitted by Yunus and Malik.
Grade: Sahih

Hadith #844 - Sahih Muslim - Anas (Sahih Muslim)
When the Messenger of Allah (ï·º) suffered from illness of which he died, and in the hadith transmitted by Ibn Mus-hir, the words are: The Messenger of Allah (ï·º) was brought till he was seated by his (Abu Bakrâs) side and the Apostle (ï·º) led the people in prayer and Abu Bakr was making takbir audible to them, and in the hadith transmitted by âIsa the (words are):â The Messenger of Allah (ï·º) sat and led the people in prayer and Abu Bakr was by his side and he was making (takbir) audib
Grade: Sahih

Hadith #846 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) breathed his last on that very day.
Grade: Sahih

Hadith #847 - Sahih Muslim - Anas (Sahih Muslim)
The last glance that I have had of the Messenger of Allah (ï·º) (before his death) was that when he on Monday drew the curtain aside. The hadith transmitted by Salih is perfect and complete.
Grade: Sahih

Hadith #849 - Sahih Muslim - Anas (Sahih Muslim)
The Apostle of Allah (ï·º) did not come to us for three days. When the prayer was about to start. Abu Bakr stepped forward (to lead the prayer), and the Messenger of Allah (ï·º) lifted the curtain. When the face of the Messenger of Allah (ï·º) became visible to us, we (found) that no sight was more endearing to us than the face of the Messenger of Allah (ï·º) as it appeared to us. The Apostle of Allah (ï·º) with the gesture of his hand directed Abu Bakr to step forward (and lead the prayer). The
Grade: Sahih

Hadith #861 - Sahih Muslim - Anas (Sahih Muslim)
Perform bowing and prostration well. By Allah, I see you even if you are behind me, or he said: (I see you) behind my back when you bow or prostrate.
Grade: Sahih

Hadith #862 - Sahih Muslim - Anas (Sahih Muslim)
The Apostle of Allah (ï·º) said: Complete the bowing and prostration well. By Allah, I see you behind my back as to how you bow and prostrate or when you bow and prostrate.
Grade: Sahih

Hadith #863 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) one day led us in the prayer. and when he completed the Prayer he turned his face towards us and said: 0 People, I am your Imam, so do not precede me in bowing and prostration and in standing and turning (faces, i. e. In pronouncing salutation), for I see you in front of me and behind me, and then said: By Him in Whose hand Is the life of Muhammad, if you could see what I see, you would have laughed little and wept much more. They said: What did you see, Messenger of
Grade: Sahih

Hadith #877 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: Straighten your rows. for the straightening of a row is a part of the perfection of prayer.
Grade: Sahih

Hadith #878 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: Complete the rows, for I can see you behind my back.
Grade: Sahih

Hadith #954 - Sahih Muslim - Anas (Sahih Muslim)
The Apostle of Allah (ï·º) used to be brief and perfect in prayer.
Grade: Sahih

Hadith #955 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) was among those whose prayers was brief and perfect.
Grade: Sahih

Hadith #956 - Sahih Muslim - Anas (Sahih Muslim)
I never prayed behind an Imam who was more brief and more perfect in prayer than the Messenger of Allah (ï·º).
Grade: Sahih

Hadith #957 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) would listen to the crying of a lad in the company of his mother, in prayer, and he would recite a short surah or a small surah.
Grade: Sahih

Hadith #958 - Sahih Muslim - Anas (Sahih Muslim)
When I begin the prayer I Intend to make it long, but I hear a boy cry. ing; I then shorten it because of his motherâs feelings.
Grade: Sahih

Hadith #1004 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: Observe moderation in prostration, and let none of you stretch out his forearms (on the ground) like a dog.
Grade: Sahih

Hadith #1075 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) came to Medina and stayed in the upper part of Medina for fourteen nights with a tribe called Banu âAmr b âAuf. He then sent for the chiefs of Banu al-Najir, and they came with swords around their inecks. He (the narrator) said: I perceive as if I am seeing the Messenger of Allah (ï·º) on his ride with Abu Bakr behind him and the chiefs of Banu al-Najjar around him till he alighted in the courtyard of Abu Ayyub. He (the narrator) said: The Messenger of Allah (ï·º
Grade: Sahih

Hadith #1076 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) used to pray in the folds of the sheep and goats before the mosque was built.
Grade: Sahih

Hadith #1082 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) used to pray towards Bait-ul-Maqdis, that it was revealed (to him):â Indeed We see the turning of the face to heaven, wherefore We shall assuredly cause thee to turn towards Qibla which shall please thee. So turn thy face towards the sacred Mosque (Kaâba)â (ii. 144). A person from Banu Salama was going; (he found the people) in rukâu (while) praying the dawn prayer and they had said one rakâah. He said in a loud voice: Listen! the Qibla has been changed and
Grade: Sahih

Hadith #1130 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: When any one of you is engaged in prayer, he is holding intimate conversation with his Lord, so none of you must spit in front of him, or towards his right side, but towards his left side under his foot.
Grade: Sahih

Hadith #1131 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: Spitting in a mosque is a sin, and its expiation is that it should be buried.
Grade: Sahih

Hadith #1141 - Sahih Muslim - Anas (Sahih Muslim)
When the supper is brought and the prayer begins, one, should first take food.
Grade: Sahih

Hadith #1142 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said: When the supper is brought before you, and it is also the time to say prayer, first take food before saying evening prayer and do not hasten (to prayer, leaving aside the food).
Grade: Sahih

Hadith #1254 - Sahih Muslim - Anas (Sahih Muslim)
A man came panting and entered the row of worshippers and said: Praise be to Allah, much praised and blessed. When the Messenger of Allah (ï·º) finished the prayer he said: Who amongst you uttered these words? The people remained silent. He (the Prophet again said) -: Who amongst you uttered these words? He said nothing wrong. Then a man said: I came and had a difficulty in breathing, so I uttered them. He replied: I saw twelve angels facing one another as to who will take them up (to Allah).
Grade: Sahih

Hadith #1303 - Sahih Muslim - Anas (Sahih Muslim)
We used to say (the noonprayer) with the Messenger of Allah (ï·º) in the intense heat, but when someone amongst us found it hard to place his forehead on the ground, he spread his cloth and prostrated on it.
Grade: Sahih

Hadith #1306 - Sahih Muslim - Anas (Sahih Muslim)
We used to offer the âAsr prayer, then one would go to Qubaâ and reach there and the sun would be still high.
Grade: Sahih

Hadith #1307 - Sahih Muslim - Anas (Sahih Muslim)
We used to offer the afternoon prayer (at such a time) that a person would go to Bani âAmr b. Auf and he would find them busy offering the afternoon prayer.
Grade: Sahih

Hadith #1310 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) led us in the afternoon prayer. When he completed it, a person from Bani Salama came to him and said: Messenger of Allah, we intend to slaughter our came and we are desirous that you should also be present there (on this occasion). He (the Holy Prophet) said: Yes. He (the person) went and we also went along with him and we found that the camel had not been slaughtered yet. Then it was slaughtered, and it was cut into pieces and then some of those were cooked, and the
Grade: Sahih

Hadith #1344 - Sahih Muslim - Anas (Sahih Muslim)
We waited for the Messenger of Allah (may peace be upon hi n) one night, till it was about midnight. He (the Holy Prophet) came and observed prayer and then turned his face towards us, as it I was seeing the lustre of the silver ring on his finger.
Grade: Sahih

Hadith #1389 - Sahih Muslim - Anas (Sahih Muslim)
I heard Jundab b. Qasri saying that the Messenger of Allah (ï·º) said: He who observed the morning prayer (in congregation), he is in fact under the protection of Allah and it never happens that Allah should make a demand in connection with the protection (that He guarantees and should not get it) for when he asks for anything in relation to His protection, he definitely secures it. He then throws him flatly in the Hell-fire.
Grade: Sahih

Hadith #1394 - Sahih Muslim - Anas (Sahih Muslim)
Stand up so that I should observe prayer (in order to bless) you Anas b. Malik said: I stood up on a mat (belonging to us) which had turned dark on account of its long use. I sprinkled water over it (in order to soften it), and the Messenger of Allah (ï·º) stood upon it, and I and an orphan formed a row behind him (the Holy Prophet) and the old woman was behind us, and the Messenger of Allah (ï·º) led us in two rakâahs of prayer and then went back.
Grade: Sahih

Hadith #1440 - Sahih Muslim - Anas (Sahih Muslim)
Allah the Exalted and Great revealed (a verse) regarding those who were killed at Biâr Maâuna, and we recited it, till it was abrogated later on (and the verse was like this):, convey to it our people the tidings that we have met our Lord, and He was pleased with us and we were pleased with Himâ.
Grade: Sahih

Hadith #1442 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) observed Qunut for a month in the dawn prayer after rukuâ and invoked curse upon Riâl, Dhakwan, and said that âUsayya had disobeyed Allah and His Apostle (ï·º).
Grade: Sahih

Hadith #1476 - Sahih Muslim - Anas (Sahih Muslim)
The Messenger of Allah (ï·º) said four rakâahs in the noon prayer while at Medina, but he offered two rakâahs in the afternoon prayer at Dhuâl-Hulaifa.
Grade: Sahih

Hadith #1477 - Sahih Muslim - Anas (Sahih Muslim)
I observed four rakâahs in the noon prayer with the Messenger of Allah (ï·º) at Medina, and said two rakâahs in the afternoon prayer at Dhuâl-Hulaifa.
Grade: Sahih

Hadith #1481 - Sahih Muslim - Anas (Sahih Muslim)
We went out from Medina to Mecca with the Messenger of Allah (ï·º) and he prayed two rakâahs at each time of prayer till we returned to Medina. I said: For how long did he stay in Mecca? He said: (For) ten (days).
Grade: Sahih

Hadith #1515 - Sahih Muslim - Anas (Sahih Muslim)
We met Anas b. Malik as he came to Syria at a place known as âAin-al-Tamar and saw him observing prayer on the back of his donkey with his face turned in that direction. (Hammam one of the narrators) pointed towards the left of Qibla, so I said to him: I find you observing prayer towards the side other than that of Qibla. Upon this he said: Had I not seen the Messenger of Allah (ï·º) doing like this, I would not have done so at all.
Grade: Sahih

Hadith #1520 - Sahih Muslim - Anas (Sahih Muslim)
When the Messenger of Allah (ï·º) set out on a journey before the sun declined (from the meridian), he delayed the noon prayer till the afternoon prayer, and then dismounted (his ride) and combined them (noon and afternoon prayers), but if the sun had declined before his setting out on a journey, he observed the noon prayer and then mounted (the ride).
Grade: Sahih

Hadith #1521 - Sahih Muslim - Anas (Sahih Muslim)
When the Messenger of Allah (ï·º) intended to combine two prayers on a journey, he delayed the noon prayer till came the early time of the afternoon prayer, and then combined the two.
Grade: Sahih

Hadith #1536 - Sahih Muslim - Anas (Sahih Muslim)
The Apostle of Allah (ï·º) used to turn to the right (at the end of the prayer).
Grade: Sahih

Hadith #1654 - Sahih Muslim - Anas (Sahih Muslim)
I asked Ibn âUmar to tell me about the practice of the Prophet (ï·º) in regard to two rakâahs before the dawn prayer: Should I make lengthy recitation in them? He said: The Messenger of Allah (ï·º) used to observe, the night prayer in pairs and then made the number odd by observing one rakâah. I said: I am not asking you about it. He said: You are a bulky man, will you not show me the patience to narrate to you the hadith completely? The Messenger of Allah (ï·º) used to observe the night p
Grade: Sahih

Hadith #1655 - Sahih Muslim - Anas (Sahih Muslim)
I asked Ibn âUmar like this (as recorded in the previous hadith) and he made this addition:â And he (the Holy Prophet) made the end of the night prayer as odd number by one rakâah.â And there is also (this addition):â Stop, stop, you are bulky.â
Grade: Sahih

Hadith #1705 - Sahih Muslim - Anas (Sahih Muslim)
I turn my face (up to Thee), I am the first of the believers; and when he raised his head from rukuâ he said: Allah listened to him who praised Him; O our Lord, praise be to Thee; and he said: He shaped (man) and how fine is his shape? And he (the narrator) said: When he pronounced salutation he said: O Allah, forgive me my earlier (sins), to the end of the hadith; and he did not say it between the Tashahhud and salutation (as mentioned above).
Grade: Sahih

Hadith #1723 - Sahih Muslim - Anas (Sahih Muslim)
What is this? They said: It is for Zainab. She prays and when she slackens or feels tired she holds it. Upon this he (the Holy Prophet) said: Untie it. Let one pray as long as one feels fresh but when one slackens or becomes tired one must stop it. (And in the hadith transmitted by Zuhair it is:â He should sit down.â )
Grade: Sahih

Hadith #1756 - Sahih Muslim - Anas (Sahih Muslim)
Allah has commanded me to recite the Qurâan to you. He said: Did Allah mention me to you by name? He (the Holy Prophet) said: Allah made a mention of your name to me. (On hearing this) Ubayy b. Kaâb wept.
Grade: Sahih

Hadith #1757 - Sahih Muslim - Anas (Sahih Muslim)
Allah has commanded me to recite to you:â Those who disbelieve were notâ¦â (al-Qurâan, xcviii. 1). He said: Did He mention me by name? He (the Prophet said): Yes. Upon this he shed tears (of gratitude).
Grade: Sahih

Hadith #1831 - Sahih Muslim - Anas (Sahih Muslim)
When we were in Medina, the moment the Muâadhdhin made the call to the sunset prayer, the people hastened to the pillars of the mosque and prayed two rakâahs with the result that any stranger coming into the mosque would think that the obligatory prayer had been observed owing to the number who were praying then.
Grade: Sahih

Hadith #1964 - Sahih Muslim - Anas (Sahih Muslim)
I saw the Messenger of Allah (ï·º) raising his hands (high enough) in supplication (for rain) that the whiteness of his armpits became visible.
Grade: Sahih

Hadith #1968 - Sahih Muslim - Anas (Sahih Muslim)
Messenger of Allah, the camels died and the passages were blocked; so supplicate Allah to send down rain upon us. The Messenger of Allah (ï·º) raised his hands and then said: (O Allah, send down rain upon us; O Allah, send dowp rain upon us; O Allah, send down rain upon us. Anas said: By Allah, we did not see any cloud or any patch of it, and there was neither any house or building standing between us and the (hillock) Salâa. There appeared a cloud in the shape of a shield from behind it, and
Grade: Sahih

Hadith #1969 - Sahih Muslim - Anas (Sahih Muslim)
The people were in the grip of famine during the lifetime of the Messenger of Allah (ï·º), and (once) as the Messenger of Allah (ï·º) was delivering the sermon standing on the pulpit on Friday, a bedouin stood up and said: Messenger of Allah, the animals died and the children suffered starvation. The rest of the hadith is the same (and the words are) that he (the Holy Prophet) said: O Allah, send down rain in our suburbs but not on us. He (the narrator) said: To whichever directions he pointed w
Grade: Sahih

Hadith #1970 - Sahih Muslim - Anas (Sahih Muslim)
Apostle of Allah, there is a drought and the trees have become yellow, the animals have died; and the rest of the hadith is the same, and in the narration transmitted by âAbd al-Aâla the words are:â The clouds cleard from Medina and it began to rain around it and not a single drop of rain fell in Medina. And as I looked towards Medina, I found it hollow like (the hollowness of) a basin.
Grade: Sahih

Hadith #1971 - Sahih Muslim - Anas (Sahih Muslim)
â Allah gathered the clouds and as we (were obliged) to stay back I saw that even the strong man, impelled by a desire to go to his family, (could not do so).â
Grade: Sahih

Hadith #1973 - Sahih Muslim - Anas (Sahih Muslim)
It rained upon us as we were with the Messenger of Allah (ï·º). The Messenger of Allah (way peace be upon him) removed his cloth (from a part of his body) till the rain fell on it. We said: Messenger of Allah, why did you do this? He said: It is because it (the rainfall) has just come from the Exalted Lord.
Grade: Sahih

Hadith #2026 - Sahih Muslim - Anas (Sahih Muslim)
Endurance is to be shown at the first blow.
Grade: Sahih

Hadith #2027 - Sahih Muslim - Anas (Sahih Muslim)
Fear Allah and show endurance. She (not recognising him) said: You have not been afflicted as I have been. When he (the Holy Prophet) had departed, it was said to her that he was the Messenger of Allah (ï·º), she was mortally shocked. She came to his door and she did not find doorkeepers at his door. She said: Messenger of Allah. I did not recognise you. He said: Endurance is to be shown at first blow, or at the first blow.
Grade: Sahih

Hadith #2035 - Sahih Muslim - Anas (Sahih Muslim)
O Hafsa, did you not hear the Messenger of Allah (ï·º) saying:â One who is lamented would be punishedâ? Suhaib also lamented over him. âUmar told him also: O Suhaib, didnât you know that one who is lamented is punished?
Grade: Sahih

Hadith #2087 - Sahih Muslim - Anas (Sahih Muslim)
There passed a bier (being carried by people) and it was lauded in good terms. Upon this the Messenger of Allah (ï·º) said: It has become certain, it has become certain, it has become certain. And there passed a bier and it was condemned in bad words. Upon this the Messenger of Allah (ï·º) said: It has become certain, it has become certain, it has become certain. âUmar said: May my father and mother be ransom for you! There passed a bier and it was praised in good terms, and you said: It has b
Grade: Sahih

Hadith #2120 - Sahih Muslim - Anas (Sahih Muslim)
I heard the Prophet (ï·º) say (while offering prayer on a dead body): O Allah! forgive him, have mercy upon him. Give him peace and absolve him. Receive him with honour and make his grave spacious. Wash him with water, snow and hail, cleanse him from faults as is cleaned a white garment from impurity. Requite him with an abode more excellent than his abode, with a family better than his family, and with a mate better than his mate, and save him from the trial of the grave and torment of Hell. â
Grade: Sahih

Hadith #2199 - Sahih Muslim - Anas (Sahih Muslim)
Abu Talha was the one among the Ansar of Medina who possessed the largest property and among his property he valued most was his garden known as Bairahaâ which was opposite the mosque, and the Messenger of Allah (ï·º) often visited it and he drank of its sweet water. When this verse was revealed: âYou will never attain righteousness till you give freely of what you loveâ (iii. 91), Abu Talha got up and, going to Allahâs Messenger (ï·º), said: Allah says in His Book: âYou will never att
Grade: Sahih

Hadith #2200 - Sahih Muslim - Anas (Sahih Muslim)
â You will not attain righteousness till you give freely of what you love,â Abu Talha said: I see that our Lord has demanded from us out of our property; so I make you a witness, Messenger of Allah. that I give my land known as Bairahaâ for the sake of Allah. Upon this the Messenger of Allah (ï·º) said: Give that to your relatives. So he gave it to Hassan b. Thabit and Ubayy b. Kaâb.
Grade: Sahih

Hadith #2296 - Sahih Muslim - Anas (Sahih Muslim)
The son of Adam grows old, but two (desires) in him remain young: desire for wealth and desire for life.
Grade: Sahih

Hadith #2299 - Sahih Muslim - Anas (Sahih Muslim)
If the son of Adam were to possess two valleys of riches. he would long for the third one. And the stomach of the son of Adam is not filled but with dust. And Allah returns to him who repents.
Grade: Sahih

Hadith #2300 - Sahih Muslim - Anas (Sahih Muslim)
I heard the Messenger of Allah (ï·º) as saying this, but I do not know whether this thing was revealed to him or not, but he said to.
Grade: Sahih

Hadith #2301 - Sahih Muslim - Anas (Sahih Muslim)
If there were two valleys of gold for the son of Adam, he would long for another one. and his mouth will not be filled but with dust, and Allah returns to him who repents.
Grade: Sahih

Hadith #2313 - Sahih Muslim - Anas (Sahih Muslim)
I was walking with the Messenger of Allah (ï·º) and he had put on a mantle of Najran with a thick border. A bedouin met him and pulled the mantle so violently that I saw this violent pulling leaving marks of the border of the mantle on the skin of the neck of the Messenger of Allah (ï·º). And he (the bedouin) said: Muhammad, issue command that I should be given out of the wealth of Allah which is at your disposal. The Messenger of Allah (ï·º) turned his attention to him and smiled, and then orde
Grade: Sahih

Hadith #2314 - Sahih Muslim - Anas (Sahih Muslim)
â He (the bedouin) pulled his (mantle) so violently that the Messenger of Allah (ï·º) was drifted very close to the bedouin.â And in the hadith transmitted by Hammam, (the words are):â He pulled it so violently that the mantle was torn and the border was left around the neck of the Messenger of Allah (ï·º).â
Grade: Sahih

Hadith #2320 - Sahih Muslim - Anas (Sahih Muslim)
May Allah grant pardon to the Messenger of Allah (ï·º) that he bestowed (these camels) upon the people of Quraish, and he ignored us, whereas our swords are still dripping blood. Anas b. Malik said: Their statement was conveyed to the Messenger of Allah (ï·º) and he sent (someone) to the Ansar and gathered them under a tent of leather. When they had assembled, the Messenger of Allah (ï·º) came to them and said: What is this news that has reached me from you? The wise people of the Ansar said: Me
Grade: Sahih

Hadith #2321 - Sahih Muslim - Anas (Sahih Muslim)
â Anas said: We could not tolerate it and he also said: The people were immature in age.â
Grade: Sahih

Hadith #2323 - Sahih Muslim - Anas (Sahih Muslim)
Is there someone alien among you? They said: No, but only the son of our sister. Upon this the Messenger of Allah (ï·º) said: The son of the sister of the people is included among the tribe, and (farther) said: The Quraish have recently abandoned Jahillyya and have just been delivered from distress; I, therefore, intend to help them and conciliate them. Donât you feel happy that the people should return with worldly riches and you return with the Messenger of Allah to your houses? (So far as m
Grade: Sahih

Hadith #2324 - Sahih Muslim - Anas (Sahih Muslim)
When Mecca was conquered, he (the Holy Prophet) distributed the spoils among the Quraish. Upon this the Ansar said: It is strange that our swords are dripping with their blood, whereas our spoils have been given to them (to the Quraish). This (remark) reached the Messenger of Allah (ï·º), and so he gathered them and said: What is this that has been conveyed to me about you? They said: (Yes) it is that very thing that, has reached you and they were not (the people) to speak a lie. Upon this he sa
Grade: Sahih

Hadith #2325 - Sahih Muslim - Anas (Sahih Muslim)
O people of Ansar! They said: At thy beck and call (are we), Messenger of Allah. Be glad we are with thee. He then turned towards his left and said: O people of Ansar. They said: At thy beck and call (are we). Be glad we are with thee. He (the Holy Prophet) was riding a white mule. He dismounted and said: I am the servant of Allah and His Apostle. The polytheists suffered defeat and the Messenger of Allah (may peace he upon him) acquired a large quantity of spoils, and he distributed them among
Grade: Sahih

Hadith #2326 - Sahih Muslim - Anas (Sahih Muslim)
We conquered Mecca and then we went on an expedition to Hunain. The polytheists came, forming themselves into the best rows that I have seen. They first formed the rows of cavalry, then those of infantry, and then those of women behind them. Then there were formed the rows of sheep and goats and then of other animals. We were also people large in number, and our (number) had reached six thousand. And on one side Khalid b. Walid was in charge of the cavalry. And our horses at once turned back fro
Grade: Sahih

Hadith #2348 - Sahih Muslim - Anas (Sahih Muslim)
â They pass through the religion clean as the arrow passes through the prey.â
Grade: Sahih

Hadith #2362 - Sahih Muslim - Anas (Sahih Muslim)
If it were not of sadaqa I would have eaten it.
Grade: Sahih

Hadith #2363 - Sahih Muslim - Anas (Sahih Muslim)
If it were not out of Sadaqa, I would have eaten it.
Grade: Sahih

Hadith #2364 - Sahih Muslim - Anas (Sahih Muslim)
Were it not (that I fear) it may be part of sadaqa, I would have eaten it.
Grade: Sahih

Hadith #2369 - Sahih Muslim - Anas (Sahih Muslim)
That is a Sadaqa for her and a gift for us.
Grade: Sahih

Hadith #2433 - Sahih Muslim - Anas (Sahih Muslim)
Take meal a little before dawn, for there is a blessing in taking meal at that time.
Grade: Sahih

Hadith #2454 - Sahih Muslim - Anas (Sahih Muslim)
Did you perceive us during the night? Upon this he said: Yes, it was this (realisation) that induced me to do that which I did. He (the narrator) said: The Messenger of Allah (ï·º) began to observe Saum Wisal at the end of the month (of Ramadan), and some persons among his Companions began to observe this uninter- rupted fast, whereupon the Messenger of Allah (ï·º) said: What about such persons who observe uninterrupted fasts? You are not like me. By Allah. if the month were lengthened for me, I
Grade: Sahih

Hadith #2455 - Sahih Muslim - Anas (Sahih Muslim)
Had the month been lengthened for me I would have continued observing Saum Wisal, so that those who act with forced hardness would (have been obliged) to abandon it. You are not like me (or he said): I am not like you. I continue to do so (in a state) that my Lord feeds me and provides me drink.
Grade: Sahih

Hadith #2506 - Sahih Muslim - Anas (Sahih Muslim)
We were with the Messenger of Allah (ï·º) on a journey. Some of us had been observing the fast and some of us had not been fasting. We got down at a place on a hot day. Most of us had the cloth for shelter. There were also those amongst us who sheltered (themselves against the rays of the) sun with the help of their hands. The observers of the fast fell down (on account of weakness). Those who had not observed it got up and pitched tents and watered the mounts. Thereupon the Messenger of Allah (
Grade: Sahih

Hadith #2507 - Sahih Muslim - Anas (Sahih Muslim)
Today the breakers of the fast have gone with the reward.
Grade: Sahih

Hadith #2877 - Sahih Muslim - Anas (Sahih Muslim)
I heard Allahâs Apostle (way peace be upon him) pronouncing Talbiya for both Hajj and Umra. Bakr (one of the narrators) said: I narrated it to Ibn âUmar, whereupon he said: He (the Holy Prophet) pronounced the Talbiya for Hajj alone. I met Anas and narrated to him the words of Ibn âUmar, whereupon he said: You treat us not but only as children. I heard Allahâs Messenger (ï·º) pronouncing Talbiya both for âUmra and Hajj.
Grade: Sahih

Hadith #2908 - Sahih Muslim - Anas (Sahih Muslim)
With (what intention) have you put on Ihram? He said: I have put on Ibram in accordance with the intention with which Allahâs Apostle (ï·º) has put on Ibram, whereupon he (the Holy Prophet) said: Had there not been the sacrificial animals with me, I would have put off Ihram (after performing âUmra).
Grade: Sahih

Hadith #2910 - Sahih Muslim - Anas (Sahih Muslim)
I heard Allahâs Messenger (ï·º) pronouncing Talbiya for both simultaneously, Talbiya for âUmra and Hajj. Talbiya for Uwra and Hajj (he performed both Hajj and Umra as a Qarin). In another version words are: I heard Allahâs Messenger (ï·º) pronouncing Talbiya for Umra and Hajj (simultaneously).â
Grade: Sahih

Hadith #2964 - Sahih Muslim - Anas (Sahih Muslim)
â Verily al-Safaâ and al-Marwa are among the Signs of Allahâ ; so whoever performs Hajj or âUmra, for him there is no harm that he should circumambulate between them.
Grade: Sahih

Hadith #3010 - Sahih Muslim - Anas (Sahih Muslim)
I heard Hajjaj b. Yusuf saying as he was delivering sermon on the pulpit: Observe the order of the (Holy) Qurâan which has been observed by Gabriel. (Thus state the surahs in this manner)â one in which mention has been made of al-Baqara,ââ one in which mention has been made of women (Surah al-Nisaâ)â and then the surah in which mention has been made of the Family of âImrin. He (the (narrator) said: I met Ibrahim and informed him about these words of his (the statement of Hajjaj b.
Grade: Sahih

Hadith #3011 - Sahih Muslim - Anas (Sahih Muslim)
I heard Hajjaj saying I Do not say Surah al-Baqara. The rest of the hadith is the same.
Grade: Sahih

Hadith #3032 - Sahih Muslim - Anas (Sahih Muslim)
Shave the other half, and said: Where is Abu Talha and gave it (the hair) to him.
Grade: Sahih

Hadith #3033 - Sahih Muslim - Anas (Sahih Muslim)
When Allahâs Messenger (ï·º) had thrown pebbles at the Jamra and had sacrificed the animal, he turned (the right side) of his head towards the barber, and i. e shaved it. He then called Abu Talha al-Ansari and gave it to him. He then turned his left side and asked him (the barber) to shave. And he (the barber) shaved. and gave it to Abu Talha and told him to distribute it amongst the people.
Grade: Sahih

Hadith #3089 - Sahih Muslim - Anas (Sahih Muslim)
Ride on It. He said: It is a sacrificial camel. Thereupon he (the Holy Prophet) said twice or thrice: Ride on it.
Grade: Sahih

Hadith #3090 - Sahih Muslim - Anas (Sahih Muslim)
Someone happened to pass by Allahâs Apostle (ï·º) with a sacrificial camel, or a sacrificial animal, whereupon he said: Ride on it. He said: It is a sacrificial camel, or animal, whereupon he said: (Ride) even if (it is a sacrificial camel).
Grade: Sahih

Hadith #3091 - Sahih Muslim - Anas (Sahih Muslim)
There happened to pass (a person) with a sacrificial camel by Allahâs Apostle (ï·º) and the rest of the hadith is the same.
Grade: Sahih

Hadith #3158 - Sahih Muslim - Anas (Sahih Muslim)
I and Abu Talha (both) came back along with Allahâs Apostle (ï·º). Safiyyah (the wife of the Holy Prophet) rode behind him on his camel and as we came to the out- skirts of Medina he said: (We are those) who return, who repent, who worship our Lord, who praise (Him), and he went on uttering this until we entered Medina.
Grade: Sahih

Hadith #3186 - Sahih Muslim - Anas (Sahih Muslim)
Ibn Khatal is hanging on to the curtains of the Kaâba, whereupon he said: Kill him. Malik (one of the narrators) attested this statement having been made.
Grade: Sahih

Hadith #3199 - Sahih Muslim - Anas (Sahih Muslim)
Find for me a servant from amongst your boys to serve me. Abu Talha went out along with me and made me sit behind him. And I used to serve Allahâs Messenger (ï·º) whenever he got down from the camel. And in one hadith he said: He proceeded and when (the mountain of) Uhud was within sight, he said: This is the mountain which loves us and we love it. And as he came close to Medina he said: O Allah, I declare (the area) between the two mountains of it (Medina) sacred just as Ibrahim declared Mecc
Grade: Sahih

Hadith #3200 - Sahih Muslim - Anas (Sahih Muslim)
â I declare sacred the area between its two lava mountains.â
Grade: Sahih

Hadith #3203 - Sahih Muslim - Anas (Sahih Muslim)
Allah bless them in their measurements, bless them in their saâs and bless them in their mudd.
Grade: Sahih

Hadith #3204 - Sahih Muslim - Anas (Sahih Muslim)
O Allah, increase in Medina twice the blessings (Thou showered) on Mecca.
Grade: Sahih

Hadith #3250 - Sahih Muslim - Anas (Sahih Muslim)
Uhud is a mountain which loves us and which we love.
Grade: Sahih

Hadith #3281 - Sahih Muslim - Anas (Sahih Muslim)
I will not marry women; someone among them said: I will not eat meat; and someone among them said: I will not lie down in bed. He (the Holy Prophet) praised Allah and glorified Him, and said: What has happened to these people that they say so and so, whereas I observe prayer and sleep too; I observe fast and suspend observing them; I marry women also? And he who turns away from my Sunnah, he has no relation with Me
Grade: Sahih

Hadith #3367 - Sahih Muslim - Anas (Sahih Muslim)
What is this? Thereupon he said: Allahâs Messenger, I have married a woman for a date-stoneâs weight of gold. He said: God bless you! Hold a wedding feast, even if only with a sheep.
Grade: Sahih

Hadith #3368 - Sahih Muslim - Anas (Sahih Muslim)
Give a feast even with a sheep.
Grade: Sahih

Hadith #3369 - Sahih Muslim - Anas (Sahih Muslim)
Hold a wedding feast, even if only with a sheep.
Grade: Sahih

Hadith #3374 - Sahih Muslim - Anas (Sahih Muslim)
Allahu Akbar (Allah is the Greatest). Khaibar is ruined. And when we get down in the valley of a people evil is the morning of the warned ones. He repeated it thrice. In the meanwhile the people went out for their work, and said: By Allah, Muhammad (has come). Abd al-âAziz or some of our companions said: Muhammad and the army (have come). He said: We took it (the territory of Khaibar) by force, and there were gathered the prisoners of war. There came Dihya and he said: Messenger of Allah, best
Grade: Sahih

Hadith #3377 - Sahih Muslim - Anas (Sahih Muslim)
I was sitting behind Abu Talha on the Day of Khaibar and my feet touched the foot of Allahâs Messenger (ï·º), and we came (to the people of Khaibar) when the sun had risen and they had driven out their cattle, and had themselves come out with their axes, large baskets and hatchets, and they said: (Here come) Muhammad and the army. Allahâs Messenger (ï·º) said: Khaibar is ruined. Verily when we get down in the valley of a people, evil is the morning of the warned ones (al-Qurâan, xxxvii. 17
Grade: Sahih

Hadith #3378 - Sahih Muslim - Anas (Sahih Muslim)
I also saw the wedding feast of Zainab, and he (the Holy Prophet) served bread and meat to the people, and made them eat to their heartâs content, and he (the Holy Prophet) sent me to call people, and as he was free (from the ceremony) he stood up and I followed him. Two persons were left and they were busy in talking and did not get out (of the apartment). He (the Holy Prophet) then proceeded towards (the apartments of) his wives. He greeted with as-Salamu âalaikum to every one of them and
Grade: Sahih

Hadith #3379 - Sahih Muslim - Anas (Sahih Muslim)
Safiyya (Allah be pleased with her) fell to the lot of Dihya in the spoils of war, and they praised her in the presence of Allahâs Messenger (ï·º) and said: We have not seen the like of her among the captives of war. He sent (a messenger) to Dihya and he gave him whatever he demanded. He then sent her to my mother and asked her to embellish her. Allahâs Messenger (ï·º) then got out of Khaibar until when he was on the other side of it, he halted, and a tent was pitched for him. When it was mo
Grade: Sahih

Hadith #3380 - Sahih Muslim - Anas (Sahih Muslim)
When the âIddah of Zainab was over, Allahâs Messenger (ï·º) said to Zaid to make a mention to her about him. Zaid went on until he came to her and she was fermenting her flour. He (Zaid) said: As I saw her I felt in my heart an idea of her greatness so much so that I could not see towards her (simply for the fact) that Allahâs Messenger (ï·º) had made a mention of her. So I turned my back towards her. and I turned upon my heels, and said: Zainab, Allahâs Messenger (ï·º) has sent (me) wit
Grade: Sahih

Hadith #3381 - Sahih Muslim - Anas (Sahih Muslim)
I did not see Allahâs Messenger (ï·º) giving a wedding feast (on the marriage) of any one (of his wives) as he did in the case of (his marriage with) Zainab, for then he sacrificed a goat (on this occasion).
Grade: Sahih

Hadith #3382 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger (ï·º) gave no better wedding feast than the one he did (on the occasion of his marriage with) Zainab. Thabit al-Bunani (one of the narrators) said: What did he serve in the wedding feast? He (Anas) said: He fed them bread and meat (so lavishly) that they (the guests) abandoned it (of their own accord after having taken them to their heartsâ content).
Grade: Sahih

Hadith #3383 - Sahih Muslim - Anas (Sahih Muslim)
When Allahâs Apostle (ï·º) married Zainab bint jahsh, he invited people (to the wedding feast) and they ate food. They then sat there and entered into conversation. He (the Holy Prophet) made a stir as if he was preparing to stand up, but (the persons busy in talking) did not stand up. When he (the Holy Prophet) saw it, he stood up and when he did so, some other persons stood up. âAsim and Abd al-Aâla in their narrations made this addition: Three (persons) sat there, and Allahâs Apostle
Grade: Sahih

Hadith #3384 - Sahih Muslim - Anas (Sahih Muslim)
I was the best informed among the people pertaining to Hijab (veil and seclusion). Ubayy b. Kaâb used to ask me about it. Anas (Allah be pleased with him) thus narrated: The Messenger of Allah (ï·º) got up in the morning as a bridegroom of Zainab bint jahsh (Allah be pleased witt her) as he had married her at Medina. He invited people to the wedding feast after the day had well risen. There sat Allahâs Messenger (ï·º) and there kept sitting along with him some persons after the people had st
Grade: Sahih

Hadith #3385 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger (ï·º) contracted marriage and he went to his wife. My mother Umm Sulaim prepared hais and placed it in an earthen vessel and said: Anas, take it to Allahâs Messenger (ï·º) and say: My mother has sent that to you and she offers greetings to you, and says that it is a humble gift for you on our behalf, Messenger of Allah. So I went along with it to Allahâs Messenger (ï·º) and said: My mother offers you salutations, and says that it is a humble gift for you on our behalf. He
Grade: Sahih

Hadith #3386 - Sahih Muslim - Anas (Sahih Muslim)
When Allahâs Apostle (ï·º) contracted marriage with Zainab (Allah be pleased with bet), Umm Sulaim sent him hats in a vessel of stone as a gift. Anas stated that Allahâs Messenger (ï·º) said to him: Go and invite on my behalf all the Muslims whom you meet. So I invited on his behalf everyone whom I met. They entered (his house) and they ate and went out. And Allahâs Messenger (ï·º) had kept his hand on the food, and he invoked blessing on that, and said whatever Allah wished him to say, an
Grade: Sahih

Hadith #3408 - Sahih Muslim - Anas (Sahih Muslim)
A person divorced his wife by three pronouncements; then another person married her and he also divorced her without having sexual intercourse with her. Then the first husband of her intended to remarry her. It was about such a case that Allahâs Messenger (ï·º) was asked, whereupon he said: No, until the second one has tasted her sweetness as the first one had tasted.
Grade: Sahih

Hadith #3503 - Sahih Muslim - Anas (Sahih Muslim)
When anyone who has already a wife marries virgin, he should stay with her for seven nights (and then turn to his other wife), but when anyone having a virgin with him (as his wife) marries a woman who has been previously married he should stay with her for three nights. Khalid (one of the narrators) said. If I were to say that it could be directly traced to the Prophet (ï·º). I would have told the truth, but he (Hadrat Anas) said: Such is the tradition.
Grade: Sahih

Hadith #3505 - Sahih Muslim - Anas (Sahih Muslim)
It is Zainab. Allahâs Apostle (ï·º) withdrew his hand. There was an altercation between the two until their voices became loud (and it was at that time) when Iqama was pronounced for prayer. There happened to come Abu Bakr and he heard their voices and said: Messenger of Allah, (kindly) come for prayer, and throw dust in their mouths. So the Prophet (ï·º) went out. âAâisha said: When Allahâs Apostle (ï·º) would finish his prayer there would also come Abu Bakr and he would do as he does (
Grade: Sahih

Hadith #3543 - Sahih Muslim - Anas (Sahih Muslim)
I asked Ibn âUmar (Allah be pleased with them) about the woman whom he had divorced. He said: I divorced her while she was in the state of menses. It was mentioned to âUmar (Allah be pleased with him) and he then made a mention of that to Allahâs Apostle (ï·º), whereupon he said: Command him to take her back and when the period of menses is over, then (he may divorce her in the state of her purity. He (Ibn Umar) said: So I took her back, then divorced her in her purity. I (the narrator) sa
Grade: Sahih

Hadith #3544 - Sahih Muslim - Anas (Sahih Muslim)
Command him to take her back and when she is pure, then divorce her. I said to Ibn âUmar Allah be pleased with them): Did you count that pronouncement of divorce? He said: Why not?
Grade: Sahih

Hadith #3700 - Sahih Muslim - Anas (Sahih Muslim)
We were forbidden that a townsman should sell for a man of the desert, even if he is his brother or father.
Grade: Sahih

Hadith #3701 - Sahih Muslim - Anas (Sahih Muslim)
We were forbidden that a townsman should sell for a man of the desert.
Grade: Sahih

Hadith #3845 - Sahih Muslim - Anas (Sahih Muslim)
Who planted this palm-a Muslim or an unbelievers The rest of the hadith is the same.
Grade: Sahih

Hadith #3848 - Sahih Muslim - Anas (Sahih Muslim)
What does the wordâ mellowâ mean? He said: (There the fruit) turns red or yellow. Donât you see if Allah had checked (the growth of) fruits; then what for the wealth of your brother would be permissible for you?
Grade: Sahih

Hadith #3849 - Sahih Muslim - Anas (Sahih Muslim)
What is meant byâ mellowâ? He said: It implies that these became red. He said: When Allah hinders the growth of fruits, (then) what for the wealth of your brother would become permissible for you?
Grade: Sahih

Hadith #3850 - Sahih Muslim - Anas (Sahih Muslim)
If Allah does not fructify them, then what is permissible for one of you to take the wealth of his brother?
Grade: Sahih

Hadith #3950 - Sahih Muslim - Anas (Sahih Muslim)
We were along with Fadala b. Ubaid (Allah be pleased with him) in an expedition. There fell to my and my friendâs lot a necklace made of gold, silver and jewels. I decided to buy that. I asked Fadala b. âUbaid, whereupon he said: Separate its gold and place it in one pan (of the balance) and place your gold in the other pan, and do not receive but equal for equal, for I heard Allahâs Messenger (ï·º) as saying: He who believes in Allah and the Hereafter should not take but equal for equal.
Grade: Sahih

Hadith #4118 - Sahih Muslim - Anas (Sahih Muslim)
What is the matter with him? They said: He had taken the vow to walk (on foot to the Kaâba). Thereupon he (Allahâs Apoitle) said: Allah is indifferent to his inflicting upon himself chastisement, and he commanded him to ride.
Grade: Sahih

Hadith #4223 - Sahih Muslim - Anas (Sahih Muslim)
If you so like, you may go to the camels of Sadaqa and drink their milk and urine. They did so and were all right. They then fell upon the shepherds and killed them and turned apostates from Islam and drove off the camels of the Prophet (ï·º). This news reached Allahâs Apostle (ï·º) and he sent (people) on their track and they were (brought) and handed over to him. He (the Holy Prophet) got their hands cut off, and their feet, and put out their eyes, and threw them on the stony ground until th
Grade: Sahih

Hadith #4224 - Sahih Muslim - Anas (Sahih Muslim)
Eight men of the tribe of âUkl came to Allahâs Messenger (ï·º) and swore allegiance to him on Islam, but found the climate of that land uncogenial to their health and thus they became sick, and they made complaint of that to Allahâs Messenger (ï·º), and he said: Why donât you go to (the fold) of our camels along with our shepherd, and make use of their milk and urine. They said: Yes. They set out and drank their (camelsâ) milk and urine and regained their health. They killed the shephe
Grade: Sahih

Hadith #4225 - Sahih Muslim - Anas (Sahih Muslim)
â Their eyes were pierced, and they were thrown on the stony ground. They were asking for water, but they were not given water.â
Grade: Sahih

Hadith #4227 - Sahih Muslim - Anas (Sahih Muslim)
There came to Allahâs Messenger (ï·º) eight persons from the tribe of âUkl, but with this addition that he did not cauterise (the wounds which hid been inflicted upon them while punishing them).
Grade: Sahih

Hadith #4228 - Sahih Muslim - Anas (Sahih Muslim)
There came to Allahâs Messenger (ï·º) some ponple from âUraina. They embraced Islam and swore allegiance to him and there had spread at that time pleurisy. The rest of the hadith is the same (but with this addition):â There were by his (the Prophetâs) side about twenty young men of the Ansar; he sent them (behind) them (culprits), and he also sent along with them one expert in following the track so that he might trace their footprints.â
Grade: Sahih

Hadith #4231 - Sahih Muslim - Anas (Sahih Muslim)
Has so and so killed you? She indicated with the nod of her head: No. He said for the second time, and she again said: No with the nod of her head. He asked for the third time, and she said: Yes with the nod of her head and Allahâs Messenger (ï·º) commanded to crush his head between two stones.
Grade: Sahih

Hadith #4235 - Sahih Muslim - Anas (Sahih Muslim)
A girl was found with her head crushed between two stones. They asked her as to who had done that-has so and so (done it) until they mentioned a Jew. She indicated with the nod of her head (that it was so). So the Jew was caught, and he made confession (of his guilt). And Allahâs Messenger (ï·º) commanded that his head be smashed with stones.
Grade: Sahih

Hadith #4244 - Sahih Muslim - Anas (Sahih Muslim)
Retribution, retribution. Umm Rubayyiâ said: Messenger of Allah, will retribution be taken from so and so? By Allah, it shall not be taken from her (i. e. from Umm Haritha). Thereupon Allahâs Apostle said: Hallowed be Allah. O Umm Rubayyiâ, Qisas (retribution is a command, prescribed) in the Book of Allah. She said: No, by Allah, Qisas will never be taken from her; and she went on saying this until they (the relatives of the one who had been injured) accepted the blood-wit. Thereupon Allah
Grade: Sahih

Hadith #4322 - Sahih Muslim - Anas (Sahih Muslim)
The mildest punishment (for drinking) is eighty (stripes) and âUmar their prescribed this punishment.
Grade: Sahih

Hadith #4324 - Sahih Muslim - Anas (Sahih Muslim)
My opinion is that you fix it as the mildest punishment. Then âUmar inflicted eighty stripes.
Grade: Sahih

Hadith #4404 - Sahih Muslim - Anas (Sahih Muslim)
There would be a flag for every perfidious person on the Day of Judgment by which he will be recognised.
Grade: Sahih

Hadith #4414 - Sahih Muslim - Anas (Sahih Muslim)
O Allah, if Thou wilt (defeat Muslims), there will be none on the earth to worship Thee.
Grade: Sahih

Hadith #4471 - Sahih Muslim - Anas (Sahih Muslim)
When the Muhajirs migrated from Mecca to Medina; they came (in a state that) they had not anything (i. e. money) in theirhands, while the Ansar possessed lands and date palms. They divided their properties with the Muhajirs. The Ansar divided and gave them on the condition that they would give half the fruit from the orchards every year, and the Muhajirs would recompense them by working with them and putting in labour. The mother of Anas b. Malik was called Umm Sulaim and she was also the mother
Grade: Sahih

Hadith #4472 - Sahih Muslim - Anas (Sahih Muslim)
No, by Allah, we will not give to, you what he has granted to me. The Prophet (ï·º) said: Umm Aiman, let him have them and for you are such and such trees instead. But she said: By Allah, there is no god besides Him. No, never! The Prophet (ï·º) continued saying: (You will get) such and such. until he had granted her ten times or nearly ten times more (than the original gift).
Grade: Sahih

Hadith #4490 - Sahih Muslim - Anas (Sahih Muslim)
Abu Bakr spoke (expressing his own views), but he (the Holy Prophet) did not pay heed to him. Then spoke âUmar (expressing his views), but he (the Holy Prophet) did not pay heed to him (too). Then Saâd b. âUbada stood up and said: Messenger of Allah, you want us (to speak). By God in Whose control is my life, if you order us to plunge our horses into the sea, we would do so. If you order us to goad our horses to the most distant place like Bark al-Ghimad, we would do so. The narrator said:
Grade: Sahih

Hadith #4501 - Sahih Muslim - Anas (Sahih Muslim)
Writeâ In the name of Allah, most Gracious and most Merciful.â Suhail said: As forâ Bismillah,â we do not know what is meant byâ Bismillah-ir-Rahman-ir-Rahimâ (In the name of Allah most Gracious and most Merciful). But write what we understand, i. e. Bi ismika allahumma (in thy name. O Allah). Then, the Prophet (ï·º) said: Write:â From Muhammad, the Messenger of Allah.â They said: If we knew that thou welt the Messenger of Allah, we would follow you. Therefore, write your name an
Grade: Sahih

Hadith #4506 - Sahih Muslim - Anas (Sahih Muslim)
When they (Companions of the Holy Prophet) were overwhelmed with grief and distress on his return from Hudaibiya where he had slaughtered his sacrificial beasts (not being allowed to proceed to Mecca), the Qurâanic verse: Inna fatahnaâ¦ laka fathan mobinan to fauzan âaziman, was revealed to him. (At this) he said: On me has descended a verse that is dearer to me than the whole world.
Grade: Sahih

Hadith #4514 - Sahih Muslim - Anas (Sahih Muslim)
How will these people attain salvation who have wounded their Prophet and broken his tooth while he called them towards God? At this time, God, the Exalted and Glorious, revealed the Verse:â Thou hast no authorityâ (iii. 127).
Grade: Sahih

Hadith #4530 - Sahih Muslim - Anas (Sahih Muslim)
Would that you approached Abdullah b. Ubayy (to persuade him to accept Islam). The Prophet (ï·º) (accordingly) went to him, riding a donkey, and (a party of) Muslims also went (with him). On the way they had to walk over a piece of land affected with salinity. When the Prophet (ï·º) approached him, he said: Do not come near me. By Allah, the obnoxious smell of your donkey has offended me. (As a rejoinder to this remark), a man from the Ansar said: By God, the smell of the donkey of the Messenger
Grade: Sahih

Hadith #4531 - Sahih Muslim - Anas (Sahih Muslim)
Who will ascertain for us what has happened to Abu Jahl? Ibn Masâud went (to gather this information). He found that the two sons of âAfraâ had struck him and he lay cold at the point of death. He caught him by his beard and said: Art thou Abu Jahl? He said: is there anybody superior to the person you have killed, or (he said) his people have killed him. Ibn Masâud says that, according to Abu Mijlaz, Abu Jahl said: Alas! a person other than a farmer would have killed me.
Grade: Sahih

Hadith #4534 - Sahih Muslim - Anas (Sahih Muslim)
God is Great. Khaibar shall face destruction. When we descend in the city-square of a people, it is a bad day for them who have been warned (and have not taken heed). He said these words thrice. The people of the town had just come out from (their houses) to go about their jobs. They said (in surprise): Muhammad has come. We captured Khaibar by force.
Grade: Sahih

Hadith #4542 - Sahih Muslim - Anas (Sahih Muslim)
O God, there is no life, but the life of the Hereafter, So forgive Thou the Ansar and the Muhajirs.
Grade: Sahih

Hadith #4549 - Sahih Muslim - Anas (Sahih Muslim)
â It is He Who restrained your hands from them and their hands from you in the valley of Mecca after He had given you a victory over them.â
Grade: Sahih

Hadith #4550 - Sahih Muslim - Anas (Sahih Muslim)
Messenger of Allah, this is Umm Sulaim. She is holding a dagger. The Messenger of Allah (ï·º) asked (her): What for are you holding this dagger? She said: I took it up so that I may tear open the belly of a polytheist who comes near me. The Messenger of Allah (ï·º) began to smile (at these words). She said: Messenger of Allah, kill all those people-other than us-whom thou hast declared to be free (on the day of the Conquest of Mecca). (They embraced Islam because) they were defeated at your hand
Grade: Sahih

Hadith #4552 - Sahih Muslim - Anas (Sahih Muslim)
On the Day of Uhud some of the people, being defeated, left the Prophet (ï·º), but Abu Talha stood before him covering him with a shield. Abu Talha was a powerful archer who broke two or three bows that day. When a man would pass by carrying a quiver containing arrows, he would say: Spare them for Abu Talha. Whenever the Prophet (ï·º) raised his head to look at the people, Abu Talha would say: Prophet of Allah, may my father and my mother be thy ransom, do not raise your head lest you be struck
Grade: Sahih

Hadith #4719 - Sahih Muslim - Anas (Sahih Muslim)
There is a blessing in the forelocks of the war horses.
Grade: Sahih

Hadith #4732 - Sahih Muslim - Anas (Sahih Muslim)
â Nobody who dies and has something good for him with Allah will (ever like to) return to this world even though he were offered the whole world and all that is in its (as an inducement), except the martyr who desires to return and be killed in the world for the (great) merit of martyrdom that he has seen.
Grade: Sahih

Hadith #4733 - Sahih Muslim - Anas (Sahih Muslim)
Nobody who enters Paradise will (ever like to) return to this world even if he were offered everything on the surface of the earth (as an inducement) except the martyr who will desire to return to this world and be killed ten times for the sake of the great honour that has been bestowed upon him.
Grade: Sahih

Hadith #4738 - Sahih Muslim - Anas (Sahih Muslim)
Leaving (for Jihad) in the way of Allah in the morning or in the evening (will merit a reward) better than the world and all that is in it.
Grade: Sahih

Hadith #4766 - Sahih Muslim - Anas (Sahih Muslim)
Messenger of Allah, I wish to fight (in the way of Allah) but I donât have anything to equip myself with for fighting. He (the Holy Prophet) said: Go to so and so, for he had equipped himself (for fighting) but he fell ill. So, he (the young man) went to him and said: The Messenger of Allah (ï·º) sends you his greetings and says that you should give me the equipage that you have provided yourself with. The man said (to his wife or maidservant): So and so, give him the equipage I have collected
Grade: Sahih

Hadith #4793 - Sahih Muslim - Anas (Sahih Muslim)
Who seeks martyrdom with sincerity shall get its reward, though he may not achieve it.
Grade: Sahih

Hadith #4884 - Sahih Muslim - Anas (Sahih Muslim)
When Allahâs Messenger (ï·º) conquered Khaibar, we caught hold of the asses outside the village. We cooked them (their flesh). Then the announcer of Allahâs Messenger (ï·º) made the announcement: Listen, verily Allah and His Messenger have prohibited you (the eating of) their (flesh), for it is a loathsome evil of Satanâs doing. Then the earthen pots were turned over along with what was in them, and these were brimming (with flesh) at that time.
Grade: Sahih

Hadith #4885 - Sahih Muslim - Anas (Sahih Muslim)
When it was the Day of Khaibar a visitor came and said: Messenger of Allah, the asses have been eaten. Then another came and said: Messenger of Allah, the asses are being destroyed. Then Allahâs Messenger (ï·º) commanded Abu Talha to make an announcement that Allah and His Messenger have prohibited you (from eating) of the flesh of (domestic) asses, for these are loathsome or impure. He (the narrator) said: The earthein pots were turned over along with what was in them.
Grade: Sahih

Hadith #4912 - Sahih Muslim - Anas (Sahih Muslim)
We chased a hare at Marr az-Zahrin (a valley near Mecca). They (my companions) ran, but felt exhausted; I also tried until I caught hold of it. I brought it to Abu Talha. He slaughtered it and sent its haunch and two hind legs to Allahâs Messenger (ï·º) through me; and he accepted them.
Grade: Sahih

Hadith #4943 - Sahih Muslim - Anas (Sahih Muslim)
He who slaughtered (the animal as a sacrifice) before the (âId) prayer. should repeat it (i. e. offer another animal). Thereupon a person stood up and said: Messenger of Allah, that is the day when meat is much desired, and he also made a mention of the need of his neighbour, and perhaps Allahâs Messenger (ï·º) attested it. He (the person who had sacrificed the animal before the âId prayer) said: I have a goat of less than one year of age with me and I like it more than two fleshy goats; s
Grade: Sahih

Hadith #4944 - Sahih Muslim - Anas (Sahih Muslim)
He who slaughtered the animal before prayer should slaughter (another animal as a sacrifice). The rest of the hadith is the same.
Grade: Sahih

Hadith #4945 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger (ï·º) addressed us on the day of âId al-Adha. He smelt the odour of flesh and he prohibited thern from slaughtering (the animals before the âId prayer), saying: He who slaughtered the animals (before the âId prayer) should do that again (as it is not valid as a sacrifice).
Grade: Sahih

Hadith #4952 - Sahih Muslim - Anas (Sahih Muslim)
I saw him sacrificing them with his own hand and saw him placing his foot on their sides, and recited the name of Allah and Glorified Him.
Grade: Sahih

Hadith #4994 - Sahih Muslim - Anas (Sahih Muslim)
I was the cup-bearer of some people in the house of Abu Talha on the day when liquor was forbidden. Their liquor had been prepared from dry dates or fresh dates when the announcer made the announcement. He (Abu Talha) said to me: Go out and find out (what the announcement is). I got out (and found) an announcer making this announcement: Behold, liquor has been declared unlawful. He said: The liquor (was spilt and) flawed in the lanes of Medina. Abu Talha said to me: Go out and Spill it, and I sp
Grade: Sahih

Hadith #4996 - Sahih Muslim - Anas (Sahih Muslim)
I was standing amongst the uncles of my tribe serving them Fadikh while I was the youngest of them, when a person came and said: Verily the use of liqour has been prohibited. They said: Anas, spill it away. So I spilt it. He (one of the narrators. Sulaiman Taimi) said that he asked Anas what that was (the Fadikh). He said: It had been prepared from unripe and ripe dates. Abu Bakr b. Anas said: It was their liquor in those days. Sulaiman said: A person narrated it to me from Anas b. Malik that he
Grade: Sahih

Hadith #4997 - Sahih Muslim - Anas (Sahih Muslim)
I was standing amongst the members of my (tribe) and serving them liquor. The rest of the hadith is the same, but with this variation that Abu Bakr b. Anas said: It was their liquor in those days (prepared from dates), and Anas was present there and he did not deny this (fact) Muâtamir reported on the authority of his father: A person who was with me told me that he had heard Anas saying that that was their liquor in those days.
Grade: Sahih

Hadith #4998 - Sahih Muslim - Anas (Sahih Muslim)
Whil Khamr was declared unlawful, the common liquor of theirs was then a mixture of dry dates and fresh dates.
Grade: Sahih

Hadith #4999 - Sahih Muslim - Anas (Sahih Muslim)
I was serving wine to Abu Talha, Abu Dujana, and Suhail b. Baidaâ from a waterskin which contained the mixture of unripe dates and fresh dates. The rest of the hadith is the same.
Grade: Sahih

Hadith #5001 - Sahih Muslim - Anas (Sahih Muslim)
I was serving drink to Abu âUbaida b. jarrah, Abu Talha and Ubayy b. Kaâb prepared from unripe dates and fresh dates when a visitor came and he said: Verily liquor has been prohibited. Thereupon, Abu Talha said: Anas, stand up and break this pitcher. I stool up and (took hold) of a pointed stone and struck the pitcher with its lower part until it broke into pieces.
Grade: Sahih

Hadith #5002 - Sahih Muslim - Anas (Sahih Muslim)
Allah revealed the verse in which Allah prohibited the use of liquor. In those days no other liquor was drunk but that prepared from dates.
Grade: Sahih

Hadith #5003 - Sahih Muslim - Anas (Sahih Muslim)
No (it is prohibited).
Grade: Sahih

Hadith #5100 - Sahih Muslim - Anas (Sahih Muslim)
I served drink to Allahâs Messenger (ï·º) in this cup of mine: honey, Nabidh, water and milk.
Grade: Sahih

Hadith #5138 - Sahih Muslim - Anas (Sahih Muslim)
We said to him: What about eating? Thereupon he (Anas) said: That is even worse and more detestable (abominable).
Grade: Sahih

Hadith #5150 - Sahih Muslim - Anas (Sahih Muslim)
It is more thirst- quenching, healthier and more wholesome. Anas said: So I also breathe three times in the course of a drink.
Grade: Sahih

Hadith #5152 - Sahih Muslim - Anas (Sahih Muslim)
(Give to one) who is on the right, then again who is on the right.
Grade: Sahih

Hadith #5153 - Sahih Muslim - Anas (Sahih Muslim)
The Apostle of Allah (may peace he upon him) came to Medina when I was ten years old and he died when I was twenty years old. My mother exhorted me to serve him. He (the Holy Prophet) came to our house, and we ruined a flabby goat for him and mixed it (the milk) with water from the well of the house. Allahâs Messenger (ï·º) drank that. Umar and Abu Bakr on his left side said to him: Allahâs Messenger, give it to Abu Bakr, but he (the Holy Prophet) gave it to the desert Arab who was on his ri
Grade: Sahih

Hadith #5154 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger (ï·º) came to our house and he asked for a drink. We milked a goat for him and then mixed it (the milk) with the water of this well of mine. I gave it to Allahâs Messenger (ï·º) and he drank it, while Abu Bakr was on his left and âUmar was in front of him, and a desert Arab was on his right. When Allahâs Messenger (ï·º) had finished the drink, Umar said: Allahâs Messenger, here is Abu Bakr, give him to drink; but Allahâs Messenger (ï·º) gave it to the desert Arab an
Grade: Sahih

Hadith #5169 - Sahih Muslim - Anas (Sahih Muslim)
When any one of you drops a mouthful he should remove anything filthy from it and then eat it, and should not leave it for the Satan. He also commanded us that we should wipe the dish saying: You do not know in what portion of your food the blessing lies.
Grade: Sahih

Hadith #5175 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger (ï·º) had a Persian neighbour who made excellent soup. He prepared some for Allahâs Messenger (ï·º) and then came to him to invite him to eat. He (Allahâs Messenger) said, âand her too,â referring to `Aisha. The man said âNo,â so Allahâs Messenger (ï·º) then said âNo.â He returned later to invite him again, so Allahâs Messenger (ï·º) said âand her too.â The man said âNo,â so Allahâs Messenger (ï·º) then said âNo.â He returned another time to
Grade: Sahih

Hadith #5179 - Sahih Muslim - Anas (Sahih Muslim)
I felt some feebleness in the voice of Allahâs Messenger (ï·º) and perceived that it was due to hunger; so have you anything with you? She said: Yes. She brought out barley loaves, then took out a head-covering of hers, in a part of which she wrapped those loaves and then put them beneath my mantle and covered me with a part of it. She then sent me to Allahâs Messenger (ï·º). I set forth and found Allahâs Messenger (ï·º) sitting in the mosque in the company of some persons. I stood near th
Grade: Sahih

Hadith #5180 - Sahih Muslim - Anas (Sahih Muslim)
Abu Talha sent me to Allahâs Messenger (ï·º) in order to invite him (for meal). She had prepared a meal. So I came and found Allahâs Messenger (ï·º) along with some people. He looked at me, and I felt shy and said: Accept the invitation of Abu Talha. He (the Holy Prophet) asked the people to get up. Thereupon Abu Talha said: Allahâs Messenger, I have prepared something for you. Allahâs Messenger (ï·º) touched (the food) and invoked blessings upon it, and then said: Let ten persons from m
Grade: Sahih

Hadith #5181 - Sahih Muslim - Anas (Sahih Muslim)
Abu Talha sent me to Allahâs Messenger (ï·º) ; the rest of the hadith is the same, but âthere is a slight variation of wording that he said at the end (The Holy Prophet) took what was left (of the food) and collected it and then invoked blessings upon it and it returned to its original state. He (the Holy Prophet) then said Take this.
Grade: Sahih

Hadith #5182 - Sahih Muslim - Anas (Sahih Muslim)
Abu Talha ordered Umm Sulaim to prepare a meal specially for Allahâs Apostle (ï·º). He then sent me to him (to the Holy Prophet) ; the rest of the hadith is the same (but there is a slight variation of wording):â Allahâs Messenger (ï·º) placed his hand and mentioned the name of Allah upon that, and then said: Admit ten men. He (Abu Talha) admitted them and they got in. He (the Holy Prophet) said: Eat while mentioning the name of Allah upon it (the meal). They ate until eighty persons had t
Grade: Sahih

Hadith #5183 - Sahih Muslim - Anas (Sahih Muslim)
â Abu Talha stood at the door (to welcome the honourable guest) until Allahâs Messenger (may peacec be upon him) came there, He (Abu Talha) said to him: Allahâs Messenger, the thing (we intend to offer you as a meal) is small in quantity. Thereupon he (the Holy Prophet) said: Bring that, for Allah will soon bless it (and increase it).
Grade: Sahih

Hadith #5185 - Sahih Muslim - Anas (Sahih Muslim)
Abu Talha saw Allahâs Messenger (ï·º) lying down upon his belly in the mosque. He came to Umm Sulaim and said: I saw Allahâs Messenger (ï·º) lying down upon the belly in the mosque, and I think he is hungry. The rest of the hadith is the same (but with the addition of these words) that Allahâs messenger (ï·º) ate (the food) and so did Abu Talha, Umm Sulaim and Anas b. Malik, but there was left some. thing which we presented to our neighbours.
Grade: Sahih

Hadith #5186 - Sahih Muslim - Anas (Sahih Muslim)
I visited Allahâs Messenger (ï·º) one day and found him sitting in the company of his Companions and talking to them, and he had tied his belly with a bandage. Usama said: I am in doubt whether there was stone on that (his belly) or not. I asked some of his Companions why Allahâs Messenger (ï·º) had bandaged his belly. They said: (He has done that to relieve) his hunger. I went to Abu Talha, the husband of Umm Sulaim, the daughter of Milhan, and said to him: Father, I saw Allahâs Messenger
Grade: Sahih

Hadith #5188 - Sahih Muslim - Anas (Sahih Muslim)
A tailor invited Allahâs Messenger (ï·º) to a meal which he had prepared. Anas b. Malik said: I went along with Allahâs Messenger (ï·º) to that feast. He presented to Allahâs Messenger (ï·º) barley bread and soup containing pumpkin, and sliced pieces of meat. Anas said: I saw Allahâs Messenger (ï·º) going after the pumpkin round the dish, so I have always liked the pumpkin since that day.
Grade: Sahih

Hadith #5189 - Sahih Muslim - Anas (Sahih Muslim)
When I saw that I began to place it before him, and did not eat it (myself). Anas said: It was since then that pumpkin was always my favourite (food).
Grade: Sahih

Hadith #5190 - Sahih Muslim - Anas (Sahih Muslim)
I heard Anas saying that any meal that was prepared for me after that I tried that it should contain pumpkin.
Grade: Sahih

Hadith #5194 - Sahih Muslim - Anas (Sahih Muslim)
I saw Allahâs Apostle (ï·º) squatting and eating dates.
Grade: Sahih

Hadith #5285 - Sahih Muslim - Anas (Sahih Muslim)
You sent it to me whereas you said what you had to, say (i. e. it is forbidden for men). Thereupon he (the Holy Prophet) said: I did not send it to you so that you might wear it, but I sent it to you so that you might derive benefit from its price.
Grade: Sahih

Hadith #5286 - Sahih Muslim - Anas (Sahih Muslim)
He who wore silk in this world would not wear it in the Hereafter.
Grade: Sahih

Hadith #5342 - Sahih Muslim - Anas (Sahih Muslim)
I perceive as if I am looking at its brightness in his hand.
Grade: Sahih

Hadith #5343 - Sahih Muslim - Anas (Sahih Muslim)
âMuhammad, the Messenger of Allah.â
Grade: Sahih

Hadith #5344 - Sahih Muslim - Anas (Sahih Muslim)
I saw one day on the finger of Allahâs Messenger (may peace be Upon him) a silver ring; so the people also got silver rings made and wore them Then Allahâs Apostle (ï·º) discarded his ring, and the people also discarded their rings.
Grade: Sahih

Hadith #5399 - Sahih Muslim - Anas (Sahih Muslim)
I was sitting with Ibn âAbbas when he gave religious verdicts but he did not say that it was Allahâs Messenger (ï·º) who had said that. However when a man said to him (Ibn âAbbas): I am the painter of these pictures. Ibn âAbbas said: I heard Allahâs Messenger (ï·º) as saying: He who painted pictures in the world would be compelled to breathe soul in them on the Day of Resurrection, but he would not be able to breathe soul (in them).
Grade: Sahih

Hadith #5411 - Sahih Muslim - Anas (Sahih Muslim)
Anas, see that nothing is given to this child until he is brought to Allahâs Apostle (ï·º) in the morning, so that he should chew some dates and touch his palate with it. I went to him in the morning and he was in the garden at that time having the mantle of Jauniyya over him and he was bus in cauterising (the camels) which had been brought to him (as spoils of war) in victory (over the enemy).
Grade: Sahih

Hadith #5412 - Sahih Muslim - Anas (Sahih Muslim)
So far as I know (he was cauterising) their ears.
Grade: Sahih

Hadith #5413 - Sahih Muslim - Anas (Sahih Muslim)
We went to Allahâs Messenger (ï·º) as he was in the fold and he was cauterising the animals of the flock and I think (he was cauterising them) on their ears. This hadith has been narrated on the authority of Shuâba through another chain of transmitters.
Grade: Sahih

Hadith #5414 - Sahih Muslim - Anas (Sahih Muslim)
I saw in the hand of Allahâs Messenger (ï·º) an instrument for cauterisation and he was cauterising the caracia collected as Zakat.
Grade: Sahih

Hadith #5440 - Sahih Muslim - Anas (Sahih Muslim)
Messenger of Allah, I did not mean you, but I called such and such (person), whereupon Allahâs Messenger (ï·º) said: You may call yourself by my name, but not by my kunya.
Grade: Sahih

Hadith #5466 - Sahih Muslim - Anas (Sahih Muslim)
I took âAbdullah b. Abi Talha Ansari to Allahâs Messenger (ï·º) at the time of his birth. Allahâs Messenger (ï·º) was at that time wearing a woollen cloak and besmearing the camels with tar. He said: Have you got with you the dates? I said: Yes. He took hold of the dates and put them in his mouth and softened them, then opened the mouth of the infant and put that in it and the child began to lick it. Thereupon Allahâs Messenger (ï·º) said: The Ansar have a liking for the dates, and he (t
Grade: Sahih

Hadith #5467 - Sahih Muslim - Anas (Sahih Muslim)
What about my child? Umm Sulaim (the wife of Abu Talha) said: He is now in a more comfortable state than before. She served him the evening meal and he took it. He then came to her (and had sexual intercourse with her) and when it was all over she said: Make arrangements for the burial of the child. When it was morning. Abu Talha came to Allahâs Messenger (ï·º) and informed him, whereupon he said: Did you spend the night with her. He said: Yes. He (the Holy Prophet) then said: O Allah, bless b
Grade: Sahih

Hadith #5476 - Sahih Muslim - Anas (Sahih Muslim)
Abu âUmair, what has the sparrow done? He (Anas) said that he had been playing with that.
Grade: Sahih

Hadith #5477 - Sahih Muslim - Anas (Sahih Muslim)
O My Son.
Grade: Sahih

Hadith #5495 - Sahih Muslim - Anas (Sahih Muslim)
I perceived as if Allahâs Messenger (ï·º) was going to pierce (his eyes).
Grade: Sahih

Hadith #5506 - Sahih Muslim - Anas (Sahih Muslim)
When the People of the Book offer you salutations, you should say: The same to you.
Grade: Sahih

Hadith #5507 - Sahih Muslim - Anas (Sahih Muslim)
The People. of the Book offer us salutations (by saying as-Salamu- âAlaikum). How should we reciprocate them? Thereupon he said: Say: Wa âAlaikum (and upon you too).
Grade: Sahih

Hadith #5531 - Sahih Muslim - Anas (Sahih Muslim)
0 so and so, she was my such and such wife. Thereupon he said, Allahâs Messenger, if I were to doubt at all, I would have entertained no doubt about you at least. Thereupon Allahâs Messenger (ï·º) said: Verily Satan circulates in the body like blood.
Grade: Sahih

Hadith #5558 - Sahih Muslim - Anas (Sahih Muslim)
I had determined to kill you. Thereupon he said: Allah will never give you the power to do it. He (the narrator) said that they (the Companionâs of the Holy Prophet) said: Should we not kill her? Thereupon he said: No. He (Anas) said: I felt (the affects of this poison) on the uvula of Allahâs Messenger.
Grade: Sahih

Hadith #5651 - Sahih Muslim - Anas (Sahih Muslim)
There is no transitive disease, no divination, but good omen pleases me, i. e. the good word or a good word. Note: The majority of scholars interpret this to mean that these things in and of themselves do not transmit or cause harm through supernatural or hidden means but that Allah is ultimately in control and any fearful superstition around these is false.
Grade: Sahih

Hadith #5652 - Sahih Muslim - Anas (Sahih Muslim)
There is no transitive disease, no divination, but good omen pleases me. It was said: What is good omen? He said: Sacred words.
Grade: Sahih

Hadith #5781 - Sahih Muslim - Anas (Sahih Muslim)
I saw during the night that which a person sees during the sleep as if we are in the house of `Uqba b. Rafi` that there was brought to us the fresh dates of Ibn Tab. I interpreted it as the sublimity for us in the world and good ending in the Hereafter and that our religion is good.
Grade: Sahih

Hadith #5791 - Sahih Muslim - Anas (Sahih Muslim)
I saw Allahâs Messenger (ï·º) during the time of the afternoon prayer and the people asking for water for performing ablution which they did not find. (A small quantity) of water was brought to Allahâs Messenger (ï·º) and he placed his hand in that vessel and commanded people to perform ablution. I saw water spouting from his fingers and the people performing ablution until the last amongst them performed it.
Grade: Sahih

Hadith #5792 - Sahih Muslim - Anas (Sahih Muslim)
Abu Hamza (the kunya of Hadrat Anas b. Malik), how many people were they? He said: They were about three hundred.
Grade: Sahih

Hadith #5841 - Sahih Muslim - Anas (Sahih Muslim)
My Cistern would be as extensive as the distance between Aila and Sanâa, of Yemen, and there would be in it jugs like stars in the sky.
Grade: Sahih

Hadith #5842 - Sahih Muslim - Anas (Sahih Muslim)
Some persons from amongst my associates would turn to my Cistern; when I would see them and they would be presented to me, they would be detained in the way while coming to me. I would say: My Lord, they are my companions, they are my companions, and it would be said to me: You donât know what innovations they made after you.
Grade: Sahih

Hadith #5843 - Sahih Muslim - Anas (Sahih Muslim)
â The vessels would be as numerous as the number of stars.
Grade: Sahih

Hadith #5844 - Sahih Muslim - Anas (Sahih Muslim)
There would be such a vast distance between the sides of my Cistern as it is between Sanaâ and Medina.
Grade: Sahih

Hadith #5846 - Sahih Muslim - Anas (Sahih Muslim)
You would be shown in it jugs of gold and silver (as numerous) as the number of stars in the sky. This hadith has been transmitted on the authority of Anas b. Malik with this addition:â More numerous than stars in the sky.â
Grade: Sahih

Hadith #5851 - Sahih Muslim - Anas (Sahih Muslim)
There was nothing to be afraid of, and he also said: We found it (this horse) like a torrent of water (indicating its swift-footedness), whereas the horse had been slow before that time.
Grade: Sahih

Hadith #5852 - Sahih Muslim - Anas (Sahih Muslim)
We have found no reason for consternation, and we have found it to be (as quick as a torrent) of water.
Grade: Sahih

Hadith #5856 - Sahih Muslim - Anas (Sahih Muslim)
I served the Messenger of Allah (ï·º) for ten years, and, by Allah, he never said to me any harsh word, and he never said to me about a thing as to why I had done that and as to why I had not done that. Abu Rabiâ has made this addition (in this narration):â The work which a servant should do.â There is no mention of his wordsâ By Allahâ.
Grade: Sahih

Hadith #5858 - Sahih Muslim - Anas (Sahih Muslim)
When Allahâs Messenger (ï·º) came to Medina, Abla Talha took hold of my hand and brought me to Allahâs Messenger (ï·º) and said: Allahâs Messenger, Anas is a prudent young boy, and he will serve you. He (Anas) said: I served him in journey and at home, but, by Allah, he never asked me about a thing which I did as to why I did so, nor about a thing which I did not do as to why I had not done that.
Grade: Sahih

Hadith #5859 - Sahih Muslim - Anas (Sahih Muslim)
I served the Messenger of Allah (ï·º) for nine years, and I do not know (of any instance) when he said to me: Why you have done this and that, and he never found fault with me in anything.
Grade: Sahih

Hadith #5860 - Sahih Muslim - Anas (Sahih Muslim)
By Allah, I would not go. I had, however, this idea in my mind that I would do as Allahâs Apostle (ï·º) had commanded me to do. I went out until I happened to come across children who had been playing in the street. In the meanwhile, Allahâs Messenger (ï·º) came there and he caught me by the back of my neck from behind me. As I looked towards him I found him smiling and he said: Unais, did you go where I commanded you to go? I said: Allahâs Messenger, yes, I am going. Anas further said: I
Grade: Sahih

Hadith #5865 - Sahih Muslim - Anas (Sahih Muslim)
O people, embrace Islam. By Allah, Muhammad donates so much as if he did not fear want. Anas said that the person embraced Islam for the sake of the world but later he became Muslim until Islam became dearer to him than the world and what it contains.
Grade: Sahih

Hadith #5869 - Sahih Muslim - Anas (Sahih Muslim)
A child was born into me this night and I named him after the name of my father Ibrihim. He then sent him to Umm Saif, the wife of a blacksmith who was called Abu Saif. He (the Holy Prophet) went to him and I followed him until we reached Abu Saif and he was blowing fire with the help of blacksmithâs bellows and the house was filled with smoke. I hastened my step and went ahead of Allahâs Messenger (ï·º) and said: Abu Saif, stop it, as there comes Allahâs Messenger (may peace he upon him).
Grade: Sahih

Hadith #5870 - Sahih Muslim - Anas (Sahih Muslim)
I have never seen anyone more kind to oneâs family than Allahâs Messenger (ï·º), and Ibrahim was sent to the suburb of Medina for suckling. He used to go there and we accompanied him. He entered the house, and it was filled with smoke as his foster-father was a bricksmith. He took him (his son Ibrihim) and kissed him and then came back. âAmr said that when Ibrihim died. Allahâs LMessenger (ï·º) said: Ibrihim is my son and he dies as a suckling babe. He has now two foster-mothers who woul
Grade: Sahih

Hadith #5880 - Sahih Muslim - Anas (Sahih Muslim)
Anjasha, drive slowly as you are driving (the mounts who are carrying) glass vessels
Grade: Sahih

Hadith #5882 - Sahih Muslim - Anas (Sahih Muslim)
Anjasha, be careful, drive slowly for you are driving the mounts who carry vessels of glass. Abu Qilaba said that Allahâs Messenger (ï·º) uttered words which if someone had uttered amongst you, you would have found fault with him.
Grade: Sahih

Hadith #5883 - Sahih Muslim - Anas (Sahih Muslim)
Anjasha, drive slowly, for you are carrying (on the camels) vessels of glass.
Grade: Sahih

Hadith #5884 - Sahih Muslim - Anas (Sahih Muslim)
Anjasha, drive slowly; do not break the vessels of glass, meaning the weak women.
Grade: Sahih

Hadith #5887 - Sahih Muslim - Anas (Sahih Muslim)
I saw when the Messenger of Allah (ï·º) got his hair cut by the barber, his Companions came round him and they eagerly wanted that no hair should fall but in the hand of a person.
Grade: Sahih

Hadith #5888 - Sahih Muslim - Anas (Sahih Muslim)
Mother of so and so, see on which side of the road you would like (to stand and talk) so that I may do the needful for you. He stood aside with her on the roadside until she got what she needed.
Grade: Sahih

Hadith #5897 - Sahih Muslim - Anas (Sahih Muslim)
I never smelt ambergris or musk as fragrant as the fragrance of the body of Allahâs Messenger (ï·º) and I never touched brocade or silk and found it as soft as the body of Allahâs Messenger (ï·º).
Grade: Sahih

Hadith #5899 - Sahih Muslim - Anas (Sahih Muslim)
Umm Sulaim, what is this that you are doing? Thereupon she said: That is your sweat which we mix in our perfume and it becomes the most fragrant perfume.
Grade: Sahih

Hadith #5900 - Sahih Muslim - Anas (Sahih Muslim)
It is Allahâs Apostle (ï·º) who is having siesta in your house, lying in your bed. She came and found him sweating and his sweat falling on the leather cloth spread on her bed. She opened her scent-bag and began to fill the bottles with it. Allahâs Apostle (ï·º) was startled and woke up and said: Umm Sulaim, what are you doing? She said: Allahâs Messenger, we seek blessings for our children through it. Thereupon he said: You have done something right.
Grade: Sahih

Hadith #5923 - Sahih Muslim - Anas (Sahih Muslim)
Allah did not blemish him with white hair.
Grade: Sahih

Hadith #5963 - Sahih Muslim - Anas (Sahih Muslim)
Paradise and Hell were presented to me and I have never seen the good and evil as (I did) today. And if you were to know you would have wept more and laughed less. He (the narrator) said: There was nothing more burdensome for the Companions of Allahâs Messenger (ï·º) than this. They covered their heads and the sound of weeping was heard from them. Then there stood up âUmar and he said: We are well pleased with Allah as our Lord, with Islam as our code of life and with Muhammad as our Apostle
Grade: Sahih

Hadith #5964 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger, who is my father? And he said: Your father is so and so, and there was revealed this verse:â Do not ask about matters which, if they were to be made manifest to you, might cause you harmâ (v. 101).
Grade: Sahih

Hadith #5965 - Sahih Muslim - Anas (Sahih Muslim)
He who desires to ask anything from me let him ask me about it. By Allah, I shall not move from this place so long as I do not inform you about that which you ask. Anas b. Malik said: People began to shed tears profusely when they heard this from Allahâs Messenger (ï·º) and Allahâs Messenger (ï·º) said it repeatedly: You ask me. Thereupon âAbdullah b. Hudhafa stood up and said: Allahâs Messenger, who is my father? He said: Your father is Hudhafa, and Allahâs Messenger (ï·º) said repeat
Grade: Sahih

Hadith #5967 - Sahih Muslim - Anas (Sahih Muslim)
Ask me and I shall leave no question of yours unanswered for you, and when the people heard about it they were overawed, as if (something tragic) was going to happen. Anas said: I began to look towards the right and the left and (found) that every person was weeping wrapping his head with the cloth. Then a person in the mosque broke the ice and they used to dispute with him by attributing his fatherhood to another man than his own father. He said: Allahâs Apostle, who is my father? He said: Yo
Grade: Sahih

Hadith #5972 - Sahih Muslim - Anas (Sahih Muslim)
If you were not to do it, it might be good for you. (So they abandoned this practice) and there was a decline in the yield. He (the Holy Prophet) happened to pass by them (and said): What has gone wrong with your trees? They said: You said so and so. Thereupon he said: You have better knowledge (of a technical skill) in the affairs of the world.
Grade: Sahih

Hadith #5982 - Sahih Muslim - Anas (Sahih Muslim)
O, the best of creation; thereupon Allahâs Messenger (ï·º) said: He is Ibrahim (peace be upon him).
Grade: Sahih

Hadith #6001 - Sahih Muslim - Anas (Sahih Muslim)
I came. And in the narration transmitted on the authority of Haddib (the words are): I happened to pass by Moses on the occasion of the Night journey near the red mound (and found him) saying his prayer in his grave.
Grade: Sahih

Hadith #6002 - Sahih Muslim - Anas (Sahih Muslim)
I happened to pass by Moses as he was busy in saying prayer in his grave, and in the hadith transmitted on the authority of âIsa there is an addition of these words:, I happened to pass on the occasion of the Night journey.â
Grade: Sahih

Hadith #6013 - Sahih Muslim - Anas (Sahih Muslim)
I saw the feet of the polytheists very close to us as we were in the cave. I said: Allahâs Messenger, if one amongst them were to see at his feet he would have surely seen us. Thereupon he said: Abu Bakr, what can befall two who have Allah as the third One with them.
Grade: Sahih

Hadith #6094 - Sahih Muslim - Anas (Sahih Muslim)
For every Umma there is a man of trust and the man of trust of this Umma is Abu âUbaida b. Jarrah.
Grade: Sahih

Hadith #6095 - Sahih Muslim - Anas (Sahih Muslim)
Send with us a person who should teach us Sunnah and al-Islam, whereupon he (the Holy Prophet) caught hold of the hand of Ubaida and said: He is a man of trust of this Umma.
Grade: Sahih

Hadith #6141 - Sahih Muslim - Anas (Sahih Muslim)
The excellence of âAâisha over women is like the excellence of Tharid over all other foods.
Grade: Sahih

Hadith #6159 - Sahih Muslim - Anas (Sahih Muslim)
I do not know whether it was because of the fasting (or for any other reason) that he (the Holy Prophet) refused to accept that. She raised her voice and showed annoyance to him.
Grade: Sahih

Hadith #6160 - Sahih Muslim - Anas (Sahih Muslim)
Let us visit Umm Aiman as Allahâs Messenger (ï·º) used to visit her. As we came to her, she wept. They (Abu Bakr and Umar) said to her: What makes you weep? What is in store (in the next world) for Allahâs-Messenger (ï·º) is better than (this worldly life). She said: I weep not because I am ignorant of the fact that what is in store for Allahâs Messenger (ï·º) (in the next world) is better than (this world), but I weep because the revelation which came from the Heaven has ceased to come. T
Grade: Sahih

Hadith #6161 - Sahih Muslim - Anas (Sahih Muslim)
I feel great compassion for her. Her brother was killed while he was with me.
Grade: Sahih

Hadith #6162 - Sahih Muslim - Anas (Sahih Muslim)
I entered Paradise and heard the noise of steps. I said: Who is it? They said: She is Ghumaisa, daughter of Milhan, the mother of Anas b. Malik.
Grade: Sahih

Hadith #6164 - Sahih Muslim - Anas (Sahih Muslim)
Do not narrate to Abu Talha about his son until I narrate it to him. Abu Talha came (home) ; she presented to him the supper. He took it and drank water. She then embellished herself which she did not do before. He (Abu Talha) had a sexual intercourse with her and when she saw that he was satisfied after sexual intercourse with her, she said: Abu Talha, if some people borrow something from another family and then (the members of the family) ask for its return, would they resist its return? He sa
Grade: Sahih

Hadith #6182 - Sahih Muslim - Anas (Sahih Muslim)
Four persons collected the Qurâan during the lifetime of Allahâs Messenger (ï·º) and all of them were Ansar: Muâadh b. Jabal, Ubayy b. Kaâb, Zaid b. Thabit, Abu Zaid. Qatada said: Anas, who was Abu Zaid? He said: He was one of my uncles.
Grade: Sahih

Hadith #6184 - Sahih Muslim - Anas (Sahih Muslim)
Verily Allah, the Exalted and Glorious, has commanded me to recite the Qurâan to you, whereupon he said: (Has) Allah mentioned my name to you? He said: Allah has mentioned your name to me. Thereupon he began to shed tears (of joy)
Grade: Sahih

Hadith #6185 - Sahih Muslim - Anas (Sahih Muslim)
I have been commanded to recite to you the Sura (al- Bayyinah) which opens with these words (Lam Yakunil-ladhiyna Kafaruu) He said: Has he mentioned to you my name? He said: Yes; thereupon he shed tears of joy.
Grade: Sahih

Hadith #6189 - Sahih Muslim - Anas (Sahih Muslim)
That his bier (that of Saâd) was placed (before them) and the Throne of the most Compassionate shook.
Grade: Sahih

Hadith #6193 - Sahih Muslim - Anas (Sahih Muslim)
By Him in Whose Hand is the life of Muhammad, the kerchiefs of Saâd b. Muâadh in Paradise are better than this.
Grade: Sahih

Hadith #6195 - Sahih Muslim - Anas (Sahih Muslim)
Who would take it from me? All the persons stretched their hands saying: I would do it, I would do it. He (Allahâs Apostle) said: Who would take it in order to fulfil its rights? Then the people withdrew their hands. Simak b. Kharasha Abu Dujana said: I am here to take it and fulfil its rights. He took it and struck the heads of the polytheists.
Grade: Sahih

Hadith #6214 - Sahih Muslim - Anas (Sahih Muslim)
O Allah, make an increase in his wealth, and progeny, and confer blessings upon him in everything Thou hast bestowed upon him.
Grade: Sahih

Hadith #6217 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger, here is a small servant of yours, invoke blessings of Allah upon him. And he invoked blessings for me (that I should be bestowed upon) every good and this was what he (said) at the end of what be supplicated for me: O Allah, make an increase in his wealth, and progeny, and cqnfer blessings (upon him) in (each one) of them.
Grade: Sahih

Hadith #6218 - Sahih Muslim - Anas (Sahih Muslim)
My mother Umm Anas came to Allahâs Messenger (ï·º). And she prepared my lower garment out of the half of her headdress and (with the other half) she covered my upper body and said: Allahâs Messenger, here is my son Unais; I have brought him to you for serving you. Invoke blessings of Allah upon him. Thereupon he (the Holy Prophet) said: O Allah, make an increase in his wealth, and progeny. Anas said: By Allah, my fortune is huge and my children, and grand-children are now more than one hundr
Grade: Sahih

Hadith #6219 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger (ï·º) passed (by our house) that my mother Umm Sulaim listened to his voice and said: Allahâs Messenger, let my father and mother be sacrificed for thee, here is Unais (and requested him to invoke blessings upon me). So Allahâs Messenger (ï·º) invoked three blessings upon me. I have seen (the results) of the two in this very world (in regard to wealth and progeny) and I hope to see (the result) of the third one in the Hereafter.
Grade: Sahih

Hadith #6220 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger (ï·º) came to me as I was playing with playmates. He greeted and sent me on an errand and I made delay in going to my mother. When I came to her she said: What detained you? I said: Allahâs Messenger (ï·º) sent me on an errand. She said: What was the purpose? I said: It is something secret. Therupon she said: Do not then divulge the secret of Allahâs Messenger (ï·º) to anyone. Anas said: By Allah, if I were to divulge it to anyone, then, O Thabit, I would have divulged it
Grade: Sahih

Hadith #6239 - Sahih Muslim - Anas (Sahih Muslim)
You are under the impression that Abu Huraira transmits so many ahadith from Allahâs Messenger (may peace up upon him) ; (bear in mind) Allah is the great Reckoner. I was a poor man and I served Allahâs Messenger (ï·º) being satisfied with bare subsistence, whereas the immigrants remained busy with transactions in the bazar; while the Ansar had been engaged in looking after their properties. (He further reported) that Allahâs Messenger (ï·º) said: He who spreads the cloth would not forget
Grade: Sahih

Hadith #6257 - Sahih Muslim - Anas (Sahih Muslim)
I think (he also sought forgiveness) for the children of the Ansar and the slaves and the freed men of the Ansar. I have no doubt about it.
Grade: Sahih

Hadith #6258 - Sahih Muslim - Anas (Sahih Muslim)
O Allah, (bear witness) (and addressing the Ansar), said: You are dearest to me amongst people, (and said: O Allah (bear witness) (and addressing the Ansar), said: You are dearest to me amongst people. And he meant Ansar.
Grade: Sahih

Hadith #6259 - Sahih Muslim - Anas (Sahih Muslim)
By Him in Whose Hand is my life, you are dearest to me amongst the people. He repeated it thrice.
Grade: Sahih

Hadith #6261 - Sahih Muslim - Anas (Sahih Muslim)
The Ansar are my family and my trusted friends. and the people would increase in number whereas they (the Ansar) would become less and less, so appreciate the deeds of those from amongst them who do good and overlook their failings.
Grade: Sahih

Hadith #6269 - Sahih Muslim - Anas (Sahih Muslim)
I set out along with Jabrir b. âAbdullah al-Bajali on a journey and he used to serve me. I said to him: Donât do that. Thereupon he said: I have seen Ansar doing this with Allahâs Messenger (ï·º). I swore by Allah whenever I accompany any one of the Ansar, I would serve him and Ibn Muthanni, and Ibn Bashshir made this addition in their narrations: Jarir was older than Anas, and Ibn Bashshir said: He was of a more advanced age as compared with Anas. Allahâs Apostle (ï·º) invoked blessings
Grade: Sahih

Hadith #6363 - Sahih Muslim - Anas (Sahih Muslim)
I heard Allahâs Messenger (ï·º) as saying: He who is desirous that his means of sustenance should be expanded for him or his age may be lengthened, should join the tie of relationship.
Grade: Sahih

Hadith #6364 - Sahih Muslim - Anas (Sahih Muslim)
He who likes that his sustenance should be expanded and his age may be lengthened should join the tie of kinship.
Grade: Sahih

Hadith #6366 - Sahih Muslim - Anas (Sahih Muslim)
Neither nurse mutual hatred, nor jealousy, nor enmity, and become as fellow brothers and servants of Allah. It is not lawful for a Muslim that he should keep his relations estranged with his brother beyond three days.
Grade: Sahih

Hadith #6370 - Sahih Muslim - Anas (Sahih Muslim)
Nurse no grudge, nurse no aversion and do not sever ties of kinship and live like fellow-brothers as servants of Allah. This hadith has been narrated on the authority of Shuâba with the same chain of transmitters but with this addition:â As Allah has commanded you.â
Grade: Sahih

Hadith #6378 - Sahih Muslim - Anas (Sahih Muslim)
â Donât sever relations of kinship, donât bear enmity against one another, donât bear aversion against one another and donât feel envy against the other and live as fellow-brothers as Allah has commanded you.
Grade: Sahih

Hadith #6464 - Sahih Muslim - Anas (Sahih Muslim)
O, it is you; you have grown young. May you not advance in years! That slave-girl returned to Umm Sulaim weeping. Umm Sulaim said: O daughter, what is the matter with you? She said: Allahâs Apostle (ï·º) has invoked curse upon me that I should not grow in age and thus I would never grow in age, or she said, in my (length) of life. Umm Sulaim went out wrapping her head-dress hurriedly until she met Allahâs Messenger (ï·º). He said to her: Umm Sulaim, what is the matter with you? She said: All
Grade: Sahih

Hadith #6486 - Sahih Muslim - Anas (Sahih Muslim)
When Allah fashioned Adam in Paradise, He left him as He liked him to leave. Then Iblis roamed round him to see what actually that was and when he found him hollow from within, he recognised that he had been created with a disposition that he would not have control over himself.
Grade: Sahih

Hadith #6546 - Sahih Muslim - Anas (Sahih Muslim)
When would be the Last Hour? Allahâs Messenger (ï·º) said: What preparation have you made for that? Thereupon he said: The love of Allah and of His Messenger (that is my preparation for the Last Hour) (for the Day of Resurrection). Thereupon he (the Holy Prophet) said: You would be along with one whom you love.
Grade: Sahih

Hadith #6547 - Sahih Muslim - Anas (Sahih Muslim)
When would be the Last Hour? He (the Holy Prophet) said: What preparation have you made for that? And he gave no details, but said: I love Allah and His Messenger. Thereupon he (the Holy Prophet) said: You would be along with one whom you love. Anas b. Malik reported through another chain of transmitters that a desert Arab came to Allahâs Messenger (may peace be upon, him), the rest of the hadith is the same but with this variation that he said: I have not made much preparations which merit ap
Grade: Sahih

Hadith #6548 - Sahih Muslim - Anas (Sahih Muslim)
When would be the Last Hour? Thereupon he (the Holy Prophet) said: What preparation have you made for the Last Hour? He said: The love of Allah and of His Messenger (is my only preparation). Thereupon he (the Holy Prophet) said: You would be along with one whom you love. Anas said: Nothing pleased us more after accepting Islam than the words of Allahâs Apostle: You would be along with one whom you love. And Anas said. I love Allah and His Messenger and Abu Bakr and Umar, and I hope that I woul
Grade: Sahih

Hadith #6549 - Sahih Muslim - Anas (Sahih Muslim)
I love, and what follows subsequently.
Grade: Sahih

Hadith #6550 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger (ï·º) and I were coming out of the mosque that we met a person on the threshold of the mosque and he said to Allahâs Messenger (ï·º): When would be the Last Hour? Allahâs Messenger (ï·º) said: What preparation have you made for that? The man became silent and then said: Allahâs Messenger, I have made no significant preparation with prayer and fasting and charity but I, however, love Allah and His Messenger. Thereupon (the Holy Prophet) said: You would be along with one
Grade: Sahih

Hadith #6565 - Sahih Muslim - Anas (Sahih Muslim)
Allah, the Exlated and Glorious, has appointed an angel as the caretaker of the womb, and he would say: My Lord, it is now a drop of semen; my Lord, It is now a clot of blood; my Lord, it has now become a lump of flesh, and when Allah decides to give it a final shape, the angel says: My Lord, would it be male or female or would he be an evil or a good person? What about his livelihood and his age? And it is all written as he is in the womb of his mother.
Grade: Sahih

Hadith #6620 - Sahih Muslim - Anas (Sahih Muslim)
It is from the conditions of the Last Hour that knowledge would be taken away and ignorance would prevail (upon the world), the liquor would be drunk, and adultery would become rampant.
Grade: Sahih

Hadith #6641 - Sahih Muslim - Anas (Sahih Muslim)
â He draws near Me by the space of a hand, I draw near him by the space (covered) by two hands.â
Grade: Sahih

Hadith #6646 - Sahih Muslim - Anas (Sahih Muslim)
When one of you makes supplication, he should supplicate with a will and should not say: O Allah, confer upon me if Thou likest, for there is none to coerce Allah.
Grade: Sahih

Hadith #6649 - Sahih Muslim - Anas (Sahih Muslim)
O Allah, keep me alive as long as there is goodness in life for me and bring death to me when there is goodness in death for me.
Grade: Sahih

Hadith #6670 - Sahih Muslim - Anas (Sahih Muslim)
Did you supplicate for anything or beg of Him about that? He said: Yes. I used to utter (these words): Impose punishment upon me earlier in this world, what Thou art going to impose upon me in the Hereafter. Thereupon Allahâs Messenger (ï·º) said: Hallowed be Allah, you have neither the power nor forbearance to take upon yourself (the burden of His Punishment). Why did you not say this: O Allah, grant us good in the world and good in the Hereafter, and save us from the torment of Fire. He (the
Grade: Sahih

Hadith #6672 - Sahih Muslim - Anas (Sahih Muslim)
You have not power enough to undergo the torment imposed by Allah. And there is no mention of: He supplicated Allah for him and He cured him.
Grade: Sahih

Hadith #6676 - Sahih Muslim - Anas (Sahih Muslim)
â Our Lord, grant us the good in this world and the good in the Hereafter and save us from the torment of Hell Fire.â
Grade: Sahih

Hadith #6706 - Sahih Muslim - Anas (Sahih Muslim)
â O Allah, I seek refuge in Thee from incapacity, from indolence, from cowardice, from senility, from miserliness, and I seek refuge in Thee from the torment of the grave and from trial of the life and death.â
Grade: Sahih

Hadith #6707 - Sahih Muslim - Anas (Sahih Muslim)
â From the trial of life and death.â
Grade: Sahih

Hadith #6709 - Sahih Muslim - Anas (Sahih Muslim)
â O Allah, I seek refuge in Thee from miserliness, from sloth and from decrepitude.â
Grade: Sahih

Hadith #6726 - Sahih Muslim - Anas (Sahih Muslim)
When you go to bed, say:â Praise is due to Allah Who fed us, provided us drink, sufficed us and provided us with shelter, for many a people there is none to suffice and none to provide shelter.â
Grade: Sahih

Hadith #6762 - Sahih Muslim - Anas (Sahih Muslim)
Allah is pleased with His servant who says: Al-Hamdu lillah while taking a morsel of food and while drinking.
Grade: Sahih

Hadith #6790 - Sahih Muslim - Anas (Sahih Muslim)
Allah is more pleased with the repentance of a servant as he turns towards Him for repentance than this that one amongst you is upon the camel in a waterless desert and there is upon (that camel) his provision of food and drink also and it is lost by him, and he having lost all hope (to get tbat) lies down in the shadow and is disappointed about his camel and there he finds that camel standing before him. He takes hold of his nosestring and then out of boundless joy says: 0 Lord, Thou art my ser
Grade: Sahih

Hadith #6791 - Sahih Muslim - Anas (Sahih Muslim)
Allah is more pleased with the repentance of His servant than if one of you gets up and he finds his camel missing in a waterless desert (and then he accidentally finds it). This hadith has been narrated on the authority of Anas b. Malik through another chain of transmitters.
Grade: Sahih

Hadith #6833 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger, I have committed an offence which deserves imposition of haad, so impose it upon me according to the Book of Allah. Thereupon he said: Were you not present with us at the time of prayer? He said: Yes. Thereupon he said: You have been granted pardon.
Grade: Sahih

Hadith #6849 - Sahih Muslim - Anas (Sahih Muslim)
Go and strike his neck. âAli came to him and he found him in a well making his body cool. âAli said to him: Come out, and as he took hold of his hand and brought him out, he found that his sexual organ had been cut. Hadrat âAli refrained from striking his neck. He came to Allahâs Apostle (ï·º) and said: Allahâs Messenger, he has not even the sexual organ with him.
Grade: Sahih

Hadith #6866 - Sahih Muslim - Anas (Sahih Muslim)
There was a person amongst us who belonged to the tribe of Bani Najjar and he recited Sura al-Baqarah and Surat Al-i-âImran and he used to transcribe for Allahâs Messenger (ï·º). He ran away as a rebel and joined the People of the Book. They gave it much importance and said: He is the person who used to transcribe for Muhammad and they were much pleased with him. Time rolled on that Allah caused his death. They dug the grave and buried him therein, but they found to their surprise that the e
Grade: Sahih

Hadith #6890 - Sahih Muslim - Anas (Sahih Muslim)
O Allah, if he is true, then shower upon us the volley of stones from the sky or inflict upon us a grievous torment, and it was on this occasion that this verse was revealed:â âAllah would never torment them so long as you are amongst them. And Allah is not going to torment them as long as they seek forgiveness. And why is it that Allah should not torment them and they prevent people from coming to the sacred mosqueâ¦.â (viii. 34) to the end.
Grade: Sahih

Hadith #6903 - Sahih Muslim - Anas (Sahih Muslim)
â The moon was split up into two parts during the life of Allahâs Messenger (ï·º).â
Grade: Sahih

Hadith #6907 - Sahih Muslim - Anas (Sahih Muslim)
Allah, the Exalted and High, would say to one who shall have to undergo the least torture (on the Day of Resurrection): Would you like to go as ransom if you had all worldly riches; he would say: Yes. Allah would say to him: When you were in the loins of Adam, I demanded from you something easier than this that you should not associate anything with Me. (The narrator says): I think He also said: I would not cause you to enter Hell-Fire but you defied and attributed Divinity (to others besides Me
Grade: Sahih

Hadith #6908 - Sahih Muslim - Anas (Sahih Muslim)
I shall cause him to enter Hell.â (The words subsequent to these) have not been mentioned.
Grade: Sahih

Hadith #6909 - Sahih Muslim - Anas (Sahih Muslim)
It would be said to the non-believers on the Day of Resurrection: If you were to possess gold, filling the whole earth, would you like to secure your freedom by paying that? He would say: Yes. Thereupon it would be said to him: Something easier (than this) was demanded from you (but you paid no heed to it).
Grade: Sahih

Hadith #6910 - Sahih Muslim - Anas (Sahih Muslim)
â It would be said to him: You have told a lie; what had been demanded from you was quite easier than this (the belief in the Oneness of Allah).â
Grade: Sahih

Hadith #6911 - Sahih Muslim - Anas (Sahih Muslim)
Allahâs Messenger, how the non-believers be made to assemble on the Day of Resurrection (by crawling) on their faces? Thereupon he said: Is He Who is powerful to make them walk on their feet not powerful enough to make them (crawl) upon their faces on the Day of Resurrection? Qatada said: Of course, it is so. (He adjured): By the might of our Lord.
Grade: Sahih

Hadith #6912 - Sahih Muslim - Anas (Sahih Muslim)
O, son of Adam, did you find any comfort, did you happen to get any material blessing? He would say: By Allah, no, my Lord. And then that person from amongst the persons of the world be brought who had led the most miserable life (in the world) from amongst the inmates of Paradise. and he would be made to dip once in Paradise and it would be said to him. 0, son of Adam, did you face, any hardship? Or had any distress fallen to your lot? And he would say: By Allah, no,0 my Lord, never did I face
Grade: Sahih

Hadith #6913 - Sahih Muslim - Anas (Sahih Muslim)
Verily, Allah does not treat a believer unjustly in regard to his virtues. He would confer upon him (His blessing) in this world and would give him reward in the Hereafter. And as regards a non-believer, he would be made to taste the reward (of virtue in this world) what he has done for himself so much that when it would be the Hereafter, he would find no virtue for which he should be rewarded.
Grade: Sahih

Hadith #6914 - Sahih Muslim - Anas (Sahih Muslim)
When a non-believer does good he is made to taste Its reward in this world. And so far as the believer is concerned, Allah stores (the reward) of his virtues for the Hereafter and provides him sustenance in accordance with his obedience to Him.
Grade: Sahih

Hadith #6953 - Sahih Muslim - Anas (Sahih Muslim)
The Paradise is surrounded by hardships and the Hell-Fire is surrounded by temptations.
Grade: Sahih

Hadith #6967 - Sahih Muslim - Anas (Sahih Muslim)
In Paradise there is a street to which they would come every Friday. The north wind will blow and would scatter fragrance on their faces and on their clothes and would add to their beauty and loveliness, and then they would go back to their family after having an added lustre to their beauty and loveliness, and their family would say to them: By Allah, you have been increased in beauty and loveliness after leaving us, and they would say: By Allah, you have also increased in beauty and loveliness
Grade: Sahih

Hadith #6998 - Sahih Muslim - Anas (Sahih Muslim)
Is there anything more, until Allah, the Exalted and High, would place His foot therein and that would say: Enough, enough, by Your Honour, and some parts of it would draw close to the other.
Grade: Sahih

Hadith #7001 - Sahih Muslim - Anas (Sahih Muslim)
There would be left some space in Paradise as Allah would like that to be left. Then Allah would create another creation as He would like.
Grade: Sahih

Hadith #7035 - Sahih Muslim - Anas (Sahih Muslim)
If you were not (to abandon) the burying of the dead (in the grave), I would have certainly supplicated Allah that He should make you listen the torment of the grave.
Grade: Sahih

Hadith #7037 - Sahih Muslim - Anas (Sahih Muslim)
When the servant is placed in his grave, his companions retrace their steps, and he hears the noise of their footsteps, two angels come to him and make him sit and say to him: What you have to say about this person (the Prophet)? If he is a believer, he would say: I bear testimony to the fact that he is a servant of Allah and His Messenger. Then it would be said to him: Look to your seat in the Hellfire, for Allah has substituted (the seat of yours) with a seat in Paradise. Allahâs Messenger (
Grade: Sahih

Hadith #7038 - Sahih Muslim - Anas (Sahih Muslim)
When the dead body. is placed in the grave, he listens to the sound of the shoes (as his friends and relatives return after burying him).
Grade: Sahih

Hadith #7039 - Sahih Muslim - Anas (Sahih Muslim)
When the servant is placed in his grave and his friends retrace their steps. The rest of the hadith is the same as transmitted by Qatada.
Grade: Sahih

Hadith #7043 - Sahih Muslim - Anas (Sahih Muslim)
We were along with Umar between Mecca and Medina that we began to look for the new moon. And I was a man with sharp eye- sight, so I could see it, but none except me saw it. I began to say to âUmar: Donât you see it? But he would not see it. Thereupon Umar said: I would soon be able to see it (when it will shine more brightly). I lay upon bed. He then made a mention of the people of Badr to us and said: Allahâs Messenger (ï·º) showed us one day before (the actual battle) the place of death
Grade: Sahih

Hadith #7044 - Sahih Muslim - Anas (Sahih Muslim)
O Abu Jahl b. Hisham, O Umayya b. Khalaf, O Utba b. Rabâila, O Shaiba b. Rabiâa, have you not found what your Lord had promised with you to be correct? As for me, I have found the promises of my Lord to be (perfectly) correct. Umar listened to the words of Allahâs Apostle (ï·º) and said: Allahâs Messenger, how do they listen and respond to you? They are dead and their bodies have decayed. Thereupon he (the Holy Prophet) said: By Him in Whose Hand is my life, what I am saying to them, eve
Grade: Sahih

Hadith #7085 - Sahih Muslim - Anas (Sahih Muslim)
And he forgot who had to forget that and. he did not make a mention of what follows after this.
Grade: Sahih

Hadith #7180 - Sahih Muslim - Anas (Sahih Muslim)
There is never a prophet who has not warned the Ummah of that one-eyed liar; behold he is one-eyed and your Lord is not one-eyed. On his forehead are the letters k f. r. (Kafir).
Grade: Sahih

Hadith #7181 - Sahih Muslim - Anas (Sahih Muslim)
There would be written three letters k. f. r., i. e. Kafir, between the eyes of the Dajjal.
Grade: Sahih

Hadith #7182 - Sahih Muslim - Anas (Sahih Muslim)
Dajjal is blind of one eye and there is written between his eyes the wordâ Kafirâ. He then spelled the word as k. f. r., which every Muslim would be able to read.
Grade: Sahih

Hadith #7206 - Sahih Muslim - Anas (Sahih Muslim)
There will be no land which would not be covered by the Dajjal but Mecca and Medina, and there would no passage out of the passages leading to them which would not be guarded by angels arranged in rows. Then he (the Dajjal) would appear in a barren place adjacent to Medina and it would rock three times that every unbeliever and hypocrite would get out of it towards him.
Grade: Sahih

Hadith #7208 - Sahih Muslim - Anas (Sahih Muslim)
The Dajjal would be followed by seventy thousand Jews of Isfahan wearing Persian shawls.
Grade: Sahih

Hadith #7220 - Sahih Muslim - Anas (Sahih Muslim)
I and the Last Hour have been sent like this. Shuâba said: I heard Qatada as saying in his narration: The excellence of one over the other. And I do not know whether he narrated it from Anas or Qatada himself said so.
Grade: Sahih

Hadith #7224 - Sahih Muslim - Anas (Sahih Muslim)
I and the Last Hour have been sent like this and (he while doing it) joined the forefinger with the middle finger.
Grade: Sahih

Hadith #7226 - Sahih Muslim - Anas (Sahih Muslim)
If this young boy lives, he may not grow very old till (he would see) the Last Hour coming to you.
Grade: Sahih

Hadith #7227 - Sahih Muslim - Anas (Sahih Muslim)
When would the Last Hour come? Thereupon Allahâs Messenger (way peace be upon him) kept quiet for a while. Then looked at a young boy in his presence belonging to the tribe of Azd Shanuâa and he said: If this boy lives he would not grow very old till the Last Hour would come to you. Anas said that this young boy was of our age during those days.
Grade: Sahih

Hadith #7228 - Sahih Muslim - Anas (Sahih Muslim)
A young boy of Mughira b. Shuâba happened to pass by (the Holy Prophet) and he was of my age. Thereupon Allahâs Apostle (ï·º) said: If he lives long he would not grow very old till the Last Hour would come (to the old people of this generation).
Grade: Sahih

Hadith #7240 - Sahih Muslim - Anas (Sahih Muslim)
Three things follow the bier of a dead man. Two of them come back and one is left with him: the members of his family, wealth and his good deeds. The members of his family and wealth come back and the deeds alone are left with him.
Grade: Sahih

Hadith #7255 - Sahih Muslim - Anas (Sahih Muslim)
We were in the company of Allahâs Messenger (ï·º) when he smiled, and said: Do you know why I laughed? We said: Allah and His Messenger, know best. Thereupon he said: It was because (there came to my mind the) talk which the servant would have with his Lord (on the Day of judgment). He would say: My Lord, have you not guaranteed me protection against injustice? He would say: Yes. Then the servant would say: I do not deem valid any witness against me but my own self, and He would say: Well, eno
Grade: Sahih

Hadith #7301 - Sahih Muslim - Anas (Sahih Muslim)
So and so sneezed and you said: May Allah have mercy upon you. I also sneezed but you did not utter these words for me. Thereupon he (the Holy Prophet) said: That person praised Allah, and you did not praise Allah.
Grade: Sahih